Medical devices comprising poly(butylene succinate) and its copolymers
Patent Information
- Application Number
- JP2023027294
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-19
- Filing Date
- 2023-02-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2039-03-01
AI Technical Summary
【0017】 手術用メッシュはポリ(ブチレンスクシネート)およびそのコポリマーの配向した繊維から調製される。改善されたメッシュはインプラント部位における組織に加わるさらなる張力を防止し、補強または修復のもとの面積を維持する。さらに、メッシュは埋め込みの後にその縁に沿ってカールせず、患者の解剖学的形状に沿い続けることも発見された。埋め込み可能なメッシュがその縁に沿ってカールすることは、隣接する組織をメッシュの縁に曝露し、組織の損傷をもたらす可能性があるので、望ましくない。
Smart Images

Figure 0007644158000018 
Figure 0007644158000019 
Figure 0007644158000020
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of and priority to U.S. Patent Application No. 62 / 636,930, filed March 1, 2018, and U.S. Patent Application No. 62 / 733,384, filed September 19, 2018, which are incorporated herein by reference in their entireties.
[0002] The present invention relates generally to resorbable polymer compositions that can be fabricated into implants or implant coatings and containers. The implants include poly(butylene succinate) and copolymers thereof. [Background technology]
[0003] 2. Background of the Invention Multifilament products made from resorbable polymers such as copolymers of glycolide and lactide, as well as monofilament products made from resorbable polymers such as polydioxanone (PDO), are well known in the art and are widely used in wound closure and general surgery. However, these products lose strength retention rapidly in vivo, and therefore their application is primarily limited to repairs that heal quickly and where long-term strength retention is not required. For example, surgeons can use resorbable multifilament sutures to access soft tissues that are not under significant tension, but surgeons generally do not use resorbable sutures when the load on the suture is significant and will remain significant for a long period of time, such as in rotator cuff repairs. Instead, surgeons will typically use permanent sutures for rotator cuff repairs, even though it may be desirable to use sutures that are fully resorbed once healing is complete. Similarly, surgeons can use resorbable monofilament sutures or meshes to access soft tissues that are not under significant tension, but surgeons generally do not use resorbable monofilament sutures or meshes when the load on the device is significant and will remain significant for a long period of time, such as in hernia repairs. Instead, surgeons will typically use a permanent (polypropylene) mesh to repair hernias, even though it would be preferable to use a device that is fully resorbable after healing is complete.
[0004] Recently, the aliphatic polyester poly(butylene succinate) (PBS) has been commercialized for use in industrial applications such as paper coatings, packaging, and mulch films (U.S. Pat. No. 7,317,069 to Aoshima, U.S. Pat. No. 8,680,229 to Maeda, U.S. Pat. No. 8,747,974 to Nakano, WO2014173055A1 to Xu, U.S. Patent Application Publication No. 20100249332 to Ferguson). The industrial polymer is produced by condensation polymerization from the readily available starting materials succinic acid and 1,4-butanediol. Xu and Guo, Biotechnol. J. 5:1149-1163 (2010), report that PB There are reviews on the industrialization of S polymers. Li et al. evaluated poly(butylene succinate) in vitro (Li et al. Macromol. Biosci. 5:433-440 (2005)). Vandesteene et al. Chin. J. Polym. Sci., 34(7):873-888 (2016) reported on the industrialization of S polymers. Structure-property relationships have been studied. Kun et al. ASAIO Journal, 58:262-267 (2012) investigated the biocompatibility of blends of PBS and polylactide. Gigli et al. Eur. Polym. J., 75:431-460 (2016) provide a review of the in vitro biocompatibility of polymers. However, the development of FDA-approved implants containing poly(butylene succinate) or its copolymers has not been successful. One reason progress in the development of implants made from PBS and its copolymers has been hampered is the poor mechanical properties of the polymers, especially compared to alternative medical grade polymers. However, it has been unsatisfactory. The low molecular weight of PBS and its copolymers has been the main cause of poor mechanical properties. The development of novel polymer synthesis methods to increase the molecular weight has been successful recently, and industrial products made from PBS and its copolymers have now been introduced. These advances in improving molecular weight relied on the use of isocyanate chemistry to increase the molecular weight of PBS and provide polymers with good mechanical properties (U.S. Pat. No. 5,349,028). Unfortunately, this approach is not a good option for the development of biocompatible degradable implants due to the toxicity associated with isocyanate chemistry. There is an ongoing need for resorbable fibers with high tensile strength and long-term strength retention in surgical practice. These fibers, including multifilament yarns and monofilament fibers, could allow surgeons to use resorbable devices instead of permanent devices when high initial strength or long-term strength retention is required. For example, monofilament resorbable fibers with high strength and long-term strength retention could be used to create monofilament surgical meshes suitable for hernia repair, breast reconstruction and mastopexy, stress urinary incontinence treatment, and pelvic floor reconstruction. Multifilament yarns with high tensile strength and long-term strength retention could also be used, for example, for rotator cuff and other ligament and tendon repair, and hernia repair, or breast augmentation. Other processing techniques, such as 3D printing, including fused filament manufacturing, could also be used to create implants with long-term strength retention, including lattice-like or other porous constructs suitable for use in hernia repair, breast reconstruction and mastopexy, stress urinary incontinence treatment, and pelvic floor reconstruction. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] U.S. Patent No. 7,317,069 [Patent Document 2] U.S. Pat. No. 8,680,229 [Patent Document 3] U.S. Pat. No. 8,747,974 [Patent Document 4] International Publication No. 2014173055 [Patent Document 5] US Patent Publication No. 20100249332 [Patent Document 6] U.S. Pat. No. 5,349,028 [Non-patent literature]
[0006] [Non-Patent Document 1] Xu and Guo, Biotechnol. J. 5:1149-1163 (2010) [Non-Patent Document 2] Li et al. Macromol. Biosci. 5:433-440 (2005) [Non-Patent Document 3] Vandesteene et al. Chin. J. Polym. Sci., 34(7):873-888 (2016) [Non-Patent Document 4] Kun et al. ASAIO Journal, 58:262-267 (2012) [Non-Patent Document 5] Gigli et al. Eur. Polym. J., 75:431-460 (2016) Summary of the Invention [Problem to be solved by the invention]
[0007] Thus, a need exists to develop a resorbable implant that has good biocompatibility, can be economically manufactured, and degrades into non-toxic degradation products, has long term strength retention, and preferably has high initial tensile strength.
[0008] It is an object of the present invention to provide biocompatible implants of poly(butylene succinate) and its copolymers that have long term strength retention.
[0009] It is a further object of the present invention to provide implants of poly(butylene succinate) and its copolymers made from oriented fibers, including monofilament and multifilament fibers.
[0010] It is a further object of the present invention to provide implants of poly(butylene succinate) and its copolymers produced by 3D printing.
[0011] Another object of the present invention is to provide a process for producing oriented implants and 3D printed implants of poly(butylene succinate) and its copolymers.
[0012] It is yet another object of the present invention to provide methods for the implantation of implants made from poly(butylene succinate) and its copolymers. [Means for solving the problem]
[0013] Summary of the Invention We have developed resorbable biocompatible implants that contain poly(butylene succinate) and its copolymers. These implants are made using poly(butylene succinate), its copolymers, or blends and are manufactured such that the implants are biocompatible, contain less than 20 endotoxin units per device as determined by the Limulus Amebocyte Lysate (LAL) assay, and are sterile. Poly(butylene succinate) polymers contain succinic acid and 1,4-butanediol, two compounds that are converted in vivo by hydrolysis to natural metabolites that degrade to carbon dioxide and water by known metabolic / catabolic pathways without the formation of toxic metabolites. Poly(butylene succinate) and its copolymers are also made without the use of crosslinkers that may result in toxic metabolites being released from the implant as the polymer degrades. The implants are particularly suitable for use in procedures requiring long-term strength retention, such as hernia repair, breast reconstruction and augmentation, mastopexy, orthopedic repair, wound management, pelvic floor reconstruction, stress urinary incontinence treatment, stent insertion, heart valve surgery, dental surgery, and other plastic surgery procedures. The preparation of the implants avoids the use of manufacturing techniques that generate endotoxins or require the use of antibiotics. Preferably, the implants are made from a polymeric composition of poly(butylene succinate) and its copolymers, the composition having a melting temperature of 105-120°C, such that the implants are stable during transportation in hot climates as well as during storage. The polymeric composition used to prepare the implants preferably excludes the use of poly(butylene succinate) and its copolymers prepared using isocyanates. In a preferred embodiment, the implants comprise a polymeric composition comprising units of 1,4-butanediol and succinic acid copolymerized with one or more hydroxycarboxylic acid units, and even more preferably, the hydroxycarboxylic acid units are malic acid, citric acid, or tartaric acid. In a particularly preferred embodiment, the implant comprises a copolyester of succinic acid-1,4-butanediol-malic acid.In another embodiment, the implant comprises a polymer composition comprising units of 1,4-butanediol and succinic acid copolymerized with maleic acid, fumaric acid, or a combination thereof. These polymer compositions may further comprise other monomers, including malic acid, citric acid, or tartaric acid.
[0014] In one embodiment, the implant is made from fibers and meshes comprising poly(butylene succinate) and its copolymers. In a preferred embodiment, the fibers are oriented. It has been discovered that oriented fibers do not curl when a non-uniform force is applied to their surface during implantation. For example, these fibers do not curl or form a pigtail-like structure when used as a suture and a non-uniform tension is applied to the suture surface. Pigtail-like suture fibers are undesirable as they make the surgical suture very difficult to handle during implantation. It has also been discovered that oriented fibers of poly(butylene succinate) and its copolymers can be prepared that do not develop indentations during degradation after implantation in vivo. This fiber characteristic provides a predictable degradation profile in vivo. This property is especially important for the performance of small and multifilament fibers. Surface pitting of small fibers, i.e., uneven erosion of the fiber surface, can result in premature loss of strength retention of the fiber, leading to premature failure of the fiber in vivo. Premature loss of strength retention is due to the reduction in effective cross-sectional area of the fiber caused by pitting. The absence of fiber pitting is especially important for any fiber-based implant, especially those where long-term strength retention is desired, such as sutures, surgical meshes, hernia meshes, breast reconstruction meshes, mastopexy meshes, and slings. The formation of pitting can be visualized using SEM as indentations, micropores, or hollowing of the fiber surface.
[0015] In one embodiment, we have developed oriented monofilament and multifilament fibers of poly(butylene succinate) and copolymers that have extremely high tensile strength, yet degrade over time in vivo. We have discovered that these fibers can be prepared using multi-stage orientation in combination with a heated conductive liquid chamber. The high tensile strength of these fibers makes them suitable for use in resorbable implant applications where high tensile strength and long-term strength retention are required. Such applications include hernia repair, breast reconstruction, urinary incontinence slings, sutures, mesh sutures, and ligament and tendon repair. In another embodiment, we have discovered that this novel fiber formation method can also be used to prepare relatively stiff oriented monofilament and multifilament fibers of poly(butylene succinate) and copolymers with Young's modulus values of 2-3 GPa. The high stiffness of these fibers is particularly advantageous in the preparation, handling, and performance of resorbable implantable sutures and surgical meshes. It has also been found that poly(butylene succinate) and copolymer compositions can be used to prepare orthopedic implants having sufficient stiffness and torsional strength to make them useful in resorbable implants such as interference screws and suture anchors.
[0016] It has also been discovered that surgical meshes can be prepared from poly(butylene succinate) and its copolymers that are dimensionally stable when implanted in vivo and do not shrink, i.e., the width and length of the mesh do not decrease substantially or significantly in dimension, for at least 4 weeks or at least 12 weeks after implantation. Table 8 shows that the relative area of the mesh does not shrink. The width and length remain relatively constant. Data for GalaFLEX mesh is shown in Table 9, but the area and dimensions of the mesh are reduced. Thus, in this embodiment, the area of the mesh is reduced by less than 6%, e.g., less than 5%, less than 4%, less than 2%, and less than 1% compared to its initial area by 12 weeks, and the area of the mesh is reduced by less than 4%, preferably less than 2%, and even more preferably 0-1% compared to its initial area at 4 weeks after implantation.
[0017] The surgical mesh is prepared from oriented fibers of poly(butylene succinate) and its copolymers. The improved mesh prevents additional tension on the tissue at the implant site and maintains the original area of reinforcement or repair. It has also been discovered that the mesh does not curl along its edges after implantation, but rather continues to conform to the patient's anatomy. Curling of an implantable mesh along its edges is undesirable as it exposes adjacent tissue to the edges of the mesh, potentially resulting in tissue damage.
[0018] In a further embodiment, the implant is produced by 3D printing a composition comprising poly(butylene succinate) and its copolymers. In a particularly preferred embodiment, the implant produced by 3D printing has a porous structure, even more preferably a lattice structure. It has been discovered that certain compositions of poly(butylene succinate) and its copolymers can be 3D printed to produce implants, and the printed polymer surprisingly has a higher weight average molecular weight than the composition from which it is derived.
[0019] In another embodiment, the implant contains one or more antimicrobial agents to prevent colonization of the implant and reduce or prevent the occurrence of infection after implantation in a patient. Coatings and containers made from forms of poly(butylene succinate) and its copolymers have also been developed for use with cardiac rhythm management devices and other implantable devices. These coatings and containers can be used to hold or partially or completely cover devices such as pacemakers, breast implants, and neurostimulators. In a preferred embodiment, the coatings and containers are made from meshes, nonwovens, films, fibers, foams, 3D printed objects, and contain antibiotics such as rifampin and minocycline. Implants containing poly(butylene succinate) and its copolymers can be sterilized by irradiation, but are more preferably sterilized by ethylene oxide gas or cold ethylene oxide gas. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is an image showing a 3D printed mesh produced by melt extrusion deposition (MED) of succinic acid-1,4-butanediol-malic acid copolyester.
[0021] [Diagram 2] FIG. 2 is an image of a paraffin-embedded tissue slide showing the histology at 20x magnification with H&E staining of a PBS mesh after 4 weeks of subcutaneous implantation in a rabbit.
[0022] [Diagram 3] FIG. 3 is an image of a paraffin-embedded tissue slide showing the histology at 200x magnification with H&E staining of a PBS mesh after 4 weeks of subcutaneous implantation in a rabbit.
[0023] [Figure 4] FIG. 4 is an SEM image at 400x magnification of oriented PBS monofilament suture fibers prior to implantation showing a smooth surface.
[0024] [Diagram 5] Figure 5 shows an SEM image of oriented PBS monofilament suture fibers after 4 weeks of implantation in a subcutaneous site in a rabbit. The image shows a smooth surface with no surface pits or localized surface erosion at 400x magnification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Detailed Description of the Invention A method has been developed to prepare resorbable implants comprising poly(butylene succinate) or copolymers thereof with long-term strength retention. These implants preferably have high initial strength and contain less than 20 endotoxin units per device as determined by limulus amebocyte lysate (LAL) assay. After implantation, the implants degrade slowly, providing sufficient time for healing before the implant loses strength. In certain embodiments, the implants are in the form of a scaffold that allows for long-term strength retention and allows tissue ingrowth to occur over an extended period of time. The implants may include one or more antimicrobial agents to prevent colonization of the implant and reduce or prevent the occurrence of infection after implantation in a patient. After implantation, the implants are designed to release antimicrobial agents. The implants may also be coated on one or more surfaces to prevent the formation of adhesions to the coated surfaces. In one embodiment, the implants may be delivered minimally invasively, and the implants may also be three-dimensional with or without the ability to recover their original shape after being deformed for delivery. The implants are particularly suitable for use in procedures requiring long term strength retention such as hernia repair, including abdominal, ventral, incisional, umbilical, inguinal, femoral, hiatal and paraesophageal hernias, breast reconstruction and augmentation, mastopexy, orthopedic repair, including ligament and tendon repair, wound management, suturing, pelvic floor reconstruction, treatment of stress urinary incontinence, stent insertion, heart valve surgery, dental surgery, and other plastic surgery. In one preferred embodiment, the implant is made of poly(butylene succinate). We have developed a method for producing implants containing highly oriented fibers and meshes of poly(butylene succinate) and its copolymers. Maintaining a high degree of orientation of these fibers and meshes is important for their physical function in vivo. The high degree of orientation of the fibers and meshes allows these devices to retain their strength over time in the body ("long-term strength retention"), thereby providing important support to tissues during reconstructive and repair procedures. If orientation is lost during the preparation of implants containing these fibers and meshes, the resulting product will have low strength and strength retention and will not be able to provide the necessary reinforcement and structure required for healing. For example, spray or dip coating oriented poly(butylene succinate) fibers using many solvents results in loss of fiber orientation and loss of strength retention. We have developed a method that allows for the preparation of fibers and meshes of poly(butylene succinate) and its copolymers without substantial loss of fiber orientation and therefore substantial loss of strength and strength retention. If desired, these implants may incorporate other bioactive agents, such as antibiotics, antimicrobials, and anti-adhesion agents.
[0026] In another preferred embodiment, a method for producing poly(butylene succinate) and copolymer implants by 3D printing including free deposition modeling, selective laser melting, and solution printing, including fused filament fabrication, fused pellet deposition, and melt extrusion deposition, has been developed. A particularly preferred 3D printing method is fused filament fabrication. In a preferred embodiment, the 3D printed poly(butylene succinate) and copolymer implants are porous, and in a particularly preferred embodiment, the implants may be latticed, including a mesh containing struts or fibers.
[0027] Methods have also been developed for preparing resorbable housings, pouches, holders, covers, meshes, nonwovens, films, folds, casings, and other containers made from poly(butylene succinate) and its copolymers that partially or completely encapsulate, surround, or hold implantable medical devices, where the poly(butylene succinate) and its copolymers optionally contain and release one or more antimicrobial agents to prevent colonization of the implant and / or reduce or prevent infection. Implantable medical devices that can be partially or completely encapsulated include cardiac rhythm management (CRM) devices (including pacemakers, defibrillators, and generators), implantable access systems, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medicines and fluids, intrathecal delivery systems, pain pumps, breast implants, and other devices for providing drugs or electrical stimulation to parts of the body.
[0028] In one embodiment, the methods disclosed herein are based on the discovery that oriented and 3D printed implants of poly(butylene succinate) and its copolymers retain their strength longer than monofilament products made from copolymers of glycolide and lactide, and polydioxanone (PDO). Oriented and 3D printed implants of poly(butylene succinate) and its copolymers can also be prepared with high initial strength.
[0029] Methods have also been developed for preparing resorbable implants comprising poly(butylene succinate) and its copolymers that can be used for the repair, regeneration, and replacement of soft and hard tissues. These implants include, but are not limited to, sutures, barbed sutures, braided sutures, monofilament sutures, hybrid sutures of monofilament and multifilament fibers, braids, ligatures, knitted or woven meshes, knitted tubes, catheters, monofilament meshes, multifilament meshes, patches, wound healing devices, bandages, wound dressings, burn dressings, ulcer dressings, skin replacements, hemostats, gastrostomies, and the like. ductal reconstruction devices, organ retrieval devices, dural replacement materials, dural patches, nerve guides, nerve regeneration or repair devices, hernia repair devices, hernia meshes, hernia plugs, devices for temporary wound or tissue support, scaffolds for tissue engineering, guided tissue repair / regeneration devices, anti-adhesion membranes, adhesion barriers, tissue isolation membranes, retention membranes, slings, devices for pelvic floor reconstruction, urethral suspension devices, devices for the treatment of urinary incontinence, devices for the treatment of vesicoureteral reflux, bladder repair devices, devices for sphincter repair, injectable particles, injectable microspheres, Bulging or filling devices, bone marrow scaffolds, clips, clamps, screws, pins, nails, medullary canal nails, bone plates, interference screws, tacks, fasteners, rivets, staples, implant fixation devices, bone graft replacements, bone void fillers, suture anchors, bone anchors, ligament repair devices, ligament strengthening devices, ligament grafts, anterior cruciate ligament repair devices, tendon repair devices, tendon grafts, tendon strengthening devices, rotator cuff repair devices, meniscus repair devices, meniscus regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, osteoarthritis devices for the treatment of, viscous supports, stents and stent coatings, including coronary, cardiovascular, peripheral, ureteral, urethral, urological, gastrointestinal, nasal, ophthalmic, or neurological stents, stent grafts, cardiovascular patches, catheter balloons, vascular closure devices, intracardiac septal defect repair devices, including but not limited to atrial septal defect repair devices and PFO (patent foramen ovale) closure devices, left atrial appendage (LAA) closure devices, pericardial patches, venous valves, heart valves, vascular grafts, myocardial regeneration devices, periodontal meshes, guided tissue regeneration membranes for periodontal tissue , ophthalmic cell implants, imaging devices, cochlear implants, embolization devices, anastomosis devices, devices for cell seeding, cell encapsulation devices, devices for controlled release, devices for drug delivery, plastic surgery devices, devices for breast lift, devices for mastopexy, devices for breast reconstruction, devices for breast enlargement, devices for breast reduction, devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift, devices for eyelid lift, devices for face lift, devices for rhytidectomy, face, eyebrows,and thread lift devices for lifting and supporting sagging neck areas, rhinoplasty devices, cheekbone augmentation devices, otoplasty devices, neck lift devices, chinoplasty devices, cosmetic repair devices, and facial scar correction devices. In particularly preferred embodiments, these implants comprise polymer compositions comprising units of 1,4-butanediol and succinic acid copolymerized with one or more hydroxycarboxylic acid units, and even more preferably, the hydroxycarboxylic acid units are malic acid, citric acid, or tartaric acid. In particularly preferred embodiments, these implants comprise a copolyester of succinic acid-1,4-butanediol-malic acid. In another embodiment, the implants comprise polymer compositions comprising units of 1,4-butanediol and succinic acid copolymerized with maleic acid, fumaric acid, or combinations thereof. These polymer compositions may further comprise other monomers, including malic acid, citric acid, or tartaric acid. I. Definition
[0030] "Bioactive agent" is used herein to mean a therapeutic, prophylactic, and / or diagnostic agent. It includes, without limitation, physiologically or pharmacologic active substances that act locally or systemically in the body. Biologically active agents are, for example, substances used to treat, prevent, diagnose, cure, or alleviate a disease or disorder, substances that affect the structure or function of the body, or prodrugs that become biologically active or more active after being placed in a given physiological environment. Bioactive agents include biologically, physiologically, or pharmacologic active substances that act locally or systemically in the human or animal body. Examples may include, but are not limited to, low molecular weight drugs, peptides, proteins, antibodies, antimicrobial agents, antibiotics, antiparasitic agents, sugars, polysaccharides, nucleotides, oligonucleotides, hyaluronic acid and its derivatives, aptamers, siRNAs, nucleic acids, and combinations thereof. "Bioactive agent" includes a single such agent and is intended to include a plurality.
[0031] "Biocompatible" as generally used herein means a biological response to a material or device that is suitable for the intended use of the device in vivo. Any metabolites or degradation products of these materials may also be biocompatible.
[0032] "Blend," as used generally herein, means a physical combination of different polymers, as opposed to a copolymer, which is made up of two or more different monomers.
[0033] "Burst strength," as used herein, unless otherwise stated, is determined using an MTS Q-Test Elite universal testing machine or similar device in accordance with ASTM D6797-02, "Standard test method for bursting strength of fabrics constant rate of extension (CRE) ball burst test," except that the test fixture uses a 3 / 8 inch diameter ball with a 1 / 2 inch diameter opening.
[0034] "Poly(butylene succinate) copolymer" as generally used herein means any polymer of succinic acid and butylene monomers incorporating one or more additional monomers. Examples of poly(butylene succinate) copolymers include poly(butylene succinate-co-adipate), poly(butylene succinate-co-terephthalate), poly(butylene succinate-co-ethylene succinate), and poly(butylene succinate-co-propylene succinate). Poly(butylene succinate-co-adipate) can be made, for example, by condensation polymerization of succinic acid, adipic acid, and 1,4-butanediol. Copolymers of poly(butylene succinate) include polymers that contain (i) units of succinic acid and 1,4-butanediol, and (ii) one or more of the following additional units, such as chain extenders, crosslinkers, and branching agents. Examples of these copolymers include succinic acid-1,4-butanediol-malic acid copolyesters, succinic acid-1,4-butanediol-citric acid copolyesters, succinic acid-1,4-butanediol-tartaric acid copolyesters, succinic acid-1,4-butanediol-malic acid copolyesters further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyesters, succinic acid-adipic acid-1,4-butanediol-citric acid copolyesters, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyesters, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyesters further comprising citric acid, tartaric acid, or a combination thereof. Copolymers of poly(butylene succinate) include polymers containing units of succinic acid and 1,4-butanediol and one or more hydroxycarboxylic acid units. The copolymers may also contain units of maleic acid or fumaric acid, or combinations thereof.
[0035] "Diameter," as generally used herein, is determined in accordance with the United States Pharmacopeia (USP) standard for surgical suture diameters (USP861).
[0036] The "elongation" or "extensibility" of a material refers to the amount of increase in length that results from the application of tension to, for example, breakage of a specimen. It is usually expressed as a percentage of the original length. (Rosato's Plastics Encyclopedia and Dictionary, Oxford Univ. Press, 1993 ).
[0037] "Endotoxin content," as used herein, means the amount of endotoxin present in a sample, as determined by the Limulus Amebocyte Lysate (LAL) assay.
[0038] "Mesh sutures," as used herein, are used to reappose soft tissues. "Mesh sutures" refers to a device that includes a needle and a mesh component that can be stitched through soft tissue and secured under tension to reappose the soft tissue. The mesh component helps prevent the suture from cutting the tissue (suture pull-out or wire cheese cutting) and increases the strength of the restoration compared to traditional monofilament and multifilament sutures.
[0039] "Molecular weight", as used herein, unless otherwise specified, means weight average molecular weight (Mw) rather than number average molecular weight (Mn) and is measured by gel permeation chromatography (GPC) against polystyrene standards.
[0040] "Orientation ratio," as used herein, is the ratio of the output speed of two godets (or rollers) used to orient a multifilament yarn or monofilament fiber to its input speed. For example, if the output speed of the multifilament yarn or monofilament fiber is 6 meters per minute and the input speed of the multifilament yarn or monofilament fiber is 2 meters per minute, then the orientation ratio is 3.
[0041] "Phosphate buffered saline", as used herein, is prepared by diluting 10X Phosphate Buffered Saline, Ultra Pure Grade (VWR, product number J373-4L) to 1X with deionized water and adding 0.05 wt% sodium azide (NaN3, Alfa Aesar, product number 14314) as a biocide. The resulting 1X buffer contains 137 mM NaCl, 2.7 mM KCl, 9.8 mM phosphate, and 0.05 wt% sodium azide, and has a pH of 7.4 at 25°C. The prepared solution is filtered through a 0.45 μm filter (VWR, product number 10040-470) before use.
[0042] "Poly(butylene succinate)" as generally used herein means an aliphatic polyester comprising units of succinic acid and 1,4-butanediol, made by condensation polymerization from succinic acid and 1,4-butanediol. Poly(butylene succinate) may be abbreviated as "PBS." Poly(butylene succinate) includes polymers of (i) units of succinic acid and 1,4-butanediol, and (ii) one or more additional monomers, including the following: chain extenders, crosslinkers, and branching agents.
[0043] "Resorbable" as generally used herein means a material that breaks down within the body and is eventually eliminated from the organism. The terms "resorbable", "degradable", "erodible", and "absorbable", with or without the prefix "bio", are used somewhat interchangeably in the literature. These terms are used interchangeably herein to describe materials that are broken down and slowly absorbed or eliminated by the organism within five years, whether the breakdown is primarily by hydrolysis or via metabolic processes.
[0044] "Strength retention" refers to the amount of time that a material maintains a particular mechanical property after implantation in a human or animal. For example, if the tensile strength of a resorbable fiber decreases by half when implanted in an animal at 3 months, then the strength retention of the fiber at 3 months is 50%.
[0045] "Suture pull-out strength" as used herein means the peak load (kg) at which the implant fails to hold the suture. It is determined using a tensile tester by clamping the implant to a horizontal holding plate, threading the suture in a loop through the implant at a distance of 1 cm from the edge of the implant, and clamping the arms of the suture in a fiber grip positioned above the implant. The test is performed at a crosshead speed of 100 mm / min, and the peak load (kg) is recorded. The suture is selected such that the implant breaks before the suture breaks.
[0046] The "Taber stiffness unit" is defined as the bending moment of 1 / 5 g applied to a specimen 1.5 inches (3.81 cm) wide and 5 cm long at an angle of 15°. It is measured using a V-5 Stiffness Tester Model 150-B or 150-E. The TABER® V-5 Stiffness Tester Model 150-B or 150-E is used to evaluate the stiffness and resilience properties of materials up to 10,000 Taber Stiffness Units. This precision instrument provides test measurements accurate to ±1.0% for specimens with thicknesses between 0.004 inches and 0.219 inches. One Taber Stiffness Unit is equal to 1 g·cm or 0.0981 mN·m. The Taber Stiffness Unit is calculated using the formula: S T =0.01419S G -0.935 to convert to Genuine Gurley™ stiffness units, where S T is the stiffness in Taber stiffness units, S G is the stiffness in Gurley stiffness units. To convert Taber stiffness units to mN m, use the formula: X=S T Use 0.098067, where X is the stiffness in mN m. These values may be used to determine relative stiffness changes or to provide a comparison between specimens of the same size when explants do not meet the size requirements of the Taber test due to limitations in the test sizes available for implantation in laboratory animals.
[0047] "Tensile strength" means the strength of a yarn or filament for a given size, measured as grams of breaking force per denier of the yarn or filament and expressed as grams per denier (gpd).
[0048] "Tensile modulus" is the ratio of stress to strain within the proportional limit of a given material.
[0049] "Tensile strength" as used herein means the maximum stress that a material can withstand while being stretched or pulled before it breaks or fractures.
[0050] "Yarn" as used herein means a continuous strand or filament of textile fiber. Yarns may be twisted or untwisted and may be substantially parallel strands. II. Composition
[0051] We have developed methods for producing resorbable implants comprising poly(butylene succinate) and its copolymers, which are used for the repair, regeneration, and replacement of soft and hard tissues.
[0052] In one embodiment, the implant comprises fibers having long-term strength retention. The fibers may be monofilament or multifilament fibers, and are preferably oriented. The fibers preferably have at least 70% strength retention at 4 weeks, more preferably at least 80% or 90% strength retention at 4 weeks in vivo. The fibers preferably have at least 50% strength retention at 12 weeks, more preferably at least 65% strength retention at 12 weeks in vivo. These properties make the fibers suitable for use in implants requiring long-term strength retention, such as hernia meshes, breast reconstruction meshes, sutures, slings for the treatment of stress urinary incontinence, mesh sutures, and pelvic floor reconstruction devices. In addition to having long term strength retention, these fibers preferably have one or more of the following properties: (i) a tensile strength greater than 400 MPa, 500 MPa, 600 MPa, 700 MPa, or 800 MPa but less than 2,000 MPa, more preferably between 400 MPa and 1,200 MPa; (ii) a Young's modulus greater than 600 MPa, 700 MPa, 800 MPa, 900 MPa, 1 GPa, or 2 GPa but less than 3 GPa; and (iii) an elongation at break of 10 to 150%, more preferably between 10 to 50%.
[0053] Methods have also been developed for producing implants comprising PBS or copolymers thereof that can partially or completely encase, surround or hold an implantable medical device, where the PBS or copolymers thereof release one or more antimicrobial agents to prevent colonization of the implantable medical device and / or reduce or prevent infection in a patient. Suitable implants comprising PBS or copolymers thereof include pouches, holders, covers, meshes, nonwovens, lattices, webs, films, foldable containers, casings, and containers.
[0054] In another embodiment, a method for preparing implants comprising relatively stiff PBS and its copolymers is described.In one embodiment, the polymer composition of PBS and its copolymers can be used to prepare orthopedic implants.These implants have sufficient stiffness and torsional strength to be suitable for use in resorbable implants such as interference screws, suture anchors, bone anchors, clips, clamps, screws, pins, nails, medullary canal nails, bone plates, interference screws, tacks, fasteners, rivets, staples, implant fixation devices, and bone void fillers.
[0055] We also describe a method for fabricating PBS and its copolymers into resorbable implants by 3D printing, a method particularly suited for creating complex 3D shapes for use as meshes, pore fillers, lattices, tissue scaffolds, and implants. A. Poly(butylene succinate)s and copolymers
[0056] The methods described herein can be used to produce resorbable implants and resorbable housings, pouches, holders, covers, meshes, nonwovens, webs, lattices, films, collapsible containers, casings, and other containers, typically from poly(butylene succinate) and its copolymers. The copolymers may contain other diols and diacids in addition to 1,4-butanediol and succinate monomers, and may alternatively or additionally contain branching agents, coupling agents, crosslinking agents, and chain extenders. Examples of diols and diacids that may be included include 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid. The copolymers may contain one or more additional diols and diacids in addition to 1,4-butanediol and succinic acid. Copolymers include, but are not limited to, poly(butylene succinate-co-adipate), poly(butylene succinate-co-terephthalate), poly(butylene succinate-co-butylene methyl succinate), poly(butylene succinate-co-butylene dimethyl succinate), poly(butylene succinate-co-ethylene succinate), and poly(butylene succinate-co-propylene succinate).
[0057] The resorbable implants described herein can be made from poly(butylene succinate) and its copolymers, the polymers or copolymers being made using one or more of the following: chain extenders or coupling agents, crosslinking agents, and branching agents. For example, poly(butylene succinate) or its copolymers can be branched or crosslinked by adding one or more of the following agents: malic acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid. A particularly preferred agent for branching or crosslinking is a hydroxycarboxylic acid unit. Preferably, the hydroxycarboxylic acid unit has two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups. In one preferred embodiment, the implant is prepared from poly(butylene succinate) containing malic acid as a branching or crosslinking agent. The compositions include poly(1,4-butylene glycol-co-succinic acid) crosslinked with malic acid, poly(butylene succinate) crosslinked with malic acid, Or succinic acid-1,4-butanediol-malic acid copolyester. It should be noted that malic acid is dehydrated to maleic or fumaric acid units at high temperatures, for example during melt extrusion. Reference herein to a PBS copolymer containing malic acid is intended to include implants in which the malic acid in the PBS copolymer undergoes further reaction during processing to form, for example, maleic or fumaric acid or another compound. Thus, an implant containing poly(butylene succinate)-malic acid copolymer refers to an implant prepared from a copolymer containing succinic acid, 1,4-butanediol, and malic acid. In another preferred embodiment, malic acid can be used as a branching or crosslinking agent to prepare a copolymer of poly(butylene succinate) and adipate, and the copolymer can be referred to as poly[(butylene succinate)-co-adipate] crosslinked with malic acid. While the malic acid disclosed herein can be the L-enantiomer, the D-enantiomer, or a combination thereof, in one preferred embodiment the poly(butylene succinate) is prepared using L-malic acid, and thus poly(1,4-butylene glycol-co-succinic acid) crosslinked with L-malic acid is one particularly preferred composition.
[0058] Agents that can be used to chain extend poly(butylene succinate) or its copolymers also include epoxides, isocyanates, diisocyanates, oxazolines, diepoxy compounds, acid anhydrides, carbonates, silicate esters, and carbodiimides. Additional monomers capable of crosslinking may be included, such as maleic acid, fumaric acid, and itaconic acid, which may be incorporated to extend the chain by the addition of peroxide. In one embodiment, copolymers with long chain branching are preferred. However, it should be noted that the use of isocyanates and diisocyanates is not preferred due to the toxicity associated with the use of these crosslinking chemistries. In one embodiment, the PBS and copolymer polymeric compositions do not include compositions prepared with isocyanates or diisocyanates. In another embodiment, the PBS and copolymer polymeric compositions do not include compositions prepared with urethane linkages. In a particularly preferred composition, the PBS and copolymer polymeric compositions used herein to prepare the implants are prepared exclusively from monomers having one or more of the following groups: hydroxyl groups and carboxylic acid groups. In another embodiment, the polymer composition of PBS and its copolymers does not contain ether linkages.
[0059] In a preferred embodiment, the poly(butylene succinate) and copolymers thereof contain at least 70%, more preferably 80%, and even more preferably 90% by weight units of succinic acid and 1,4-butanediol.
[0060] In another embodiment, the poly(butylene succinate) and copolymers thereof disclosed herein include polymers and copolymers enriched with known isotopes of hydrogen, carbon, and / or oxygen. Hydrogen has three naturally occurring isotopes, including: 1 H (protium), 2 H (deuterium), and 3 H (tritium), the most common of which is 1The isotope content of the polymer or copolymer can be, for example, enriched, whereby the polymer or copolymer contains a higher than natural ratio of a particular isotope. The carbon and oxygen content of the polymer or copolymer can also be enriched, including, but not limited to, 13 C. 14 C. 17 O, or 18 It may contain higher than natural ratios of carbon and oxygen isotopes, including O.
[0061] Other isotopes of carbon, hydrogen, and oxygen are known to those of skill in the art.
[0062] The preferred hydrogen isotope enriched in the poly(butylene succinate) or copolymer thereof is deuterium, i.e., deuterated poly(butylene succinate) or copolymer thereof. The deuterated percentage is at least 1%, up to 5, 1 It may be up to 0, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or 85% or more.
[0063] Preferred polymers and copolymers have a weight average molecular weight (Mw) based on gel permeation chromatography (GPC) versus polystyrene standards of 10,000 to 400,000, more preferably 50,000 to 300,000, even more preferably 100,000 to 200,000. In a particularly preferred embodiment, the polymers and copolymers have a weight average molecular weight of 50,000 to 300,000, more preferably 75,000 to 300,000.
[0064] In a preferred embodiment, the tensile strength in the unoriented form of the poly(butylene succinate) or its copolymers used to make the implant may be at least 1 MPa, preferably 10 MPa, more preferably 35 MPa, even more preferably up to 70 MPa or higher. A particularly preferred tensile range in the unoriented form is 35-60 MPa. The Young's modulus in the unoriented form of the poly(butylene succinate) or its copolymers used to make the implant may preferably range from 30-700 MPa, more preferably 300-500 MPa, depending on its crystallinity. It is also preferred that the polymer or copolymer has a melting point of at least 80°C, preferably 90°C, even more preferably higher than 100°C. In a preferred embodiment, the melting point of the poly(butylene succinate) or its copolymers used to make the implant is 115°C±20°C, more preferably 105°C-120°C. A higher melting point (above 100°C) is preferred, especially to improve the stability of the implant during sterilization, transportation and storage.
[0065] In one preferred embodiment, the poly(butylene succinate) or copolymers thereof used to prepare the implant have the following properties: 1.23 to 1.26 g / cm 3 a density of -31°C to -35°C, a glass transition temperature of 113°C to 117°C, a melting point of 200°C to 210°C, a melt flow rate (MFR) at 190°C / 2.16kgf of 2 to 10g / 10min, and a tensile strength of 30 to 60MPa.
[0066] In a particularly preferred embodiment, it is important that poly(butylene succinate) or its copolymers have low moisture content during processing and storage. This is necessary to ensure that implants with high tensile strength, long-term strength retention, and good product life can be produced. In a preferred embodiment, the polymers and copolymers used to prepare the implants have a moisture content of less than 1,000 ppm (0.1 wt%), less than 500 ppm (0.05 wt%), less than 300 ppm (0.03 wt%), more preferably less than 100 ppm (0.01 wt%), and even more preferably less than 50 ppm (0.005 wt%).
[0067] The composition used to prepare the implant must have low endotoxin content.The endotoxin content must be low enough that the implant made of poly(butylene succinate) or its copolymer has an endotoxin content of less than 20 endotoxin units per device as determined by limulus amebocyte lysate (LAL) assay.In one embodiment, the composition has PBS or its copolymer with an endotoxin content of less than 2.5EU / g. B. Additives and other polymers
[0068] Certain additives may be incorporated into poly(butylene succinate) and its copolymers prior to converting these compositions into resorbable implants. Preferably, these additives are incorporated during the compounding process to produce pellets that can be subsequently processed into implants. For example, additives may be incorporated into poly(butylene succinate) and its copolymers. The compounded poly(butylene succinate) or copolymer is extruded into pellets, and the pellets are 3D printed or extruded into fibers suitable for making an implantable surgical mesh, for example by knitting, weaving, or 3D printing. In another embodiment, the additive may be incorporated using a solution-based process. In a preferred embodiment of the invention, the additive is biocompatible, and even more preferably, the additive is both biocompatible and resorbable.
[0069] In one embodiment of the present invention, the additives may be nucleating agents and / or plasticizers. These additives may be added in sufficient amounts to obtain the desired results. Generally, these additives may be added in amounts up to 20% by weight. Nucleating agents are incorporated to increase the crystallization rate of poly(butylene succinate) or its copolymers. Such agents may be used, for example, to improve the mechanical properties of fibers and meshes and implants, and to reduce cycle times. Preferred nucleating agents include, but are not limited to, salts of organic acids such as calcium citrate, polymers or oligomers of poly(butylene succinate) polymers and copolymers, high melting point polymers such as polyglycolic acid and polylactic acid, alpha-cyclodextrin, talc, micronized mica, calcium carbonate, ammonium chloride, and aromatic amino acids such as tyrosine and phenylalanine.
[0070] Plasticizers that may be incorporated into the composition include, but are not limited to, di-n-butyl maleate, methyl laurate, dibutyl fumarate, di(2-ethylhexyl)(dioctyl) maleate, paraffin, dodecanol, olive oil, soybean oil, polytetramethylene glycol, methyl oleate, n-propyl oleate, tetrahydrofurfuryl oleate, epoxidized linseed oil, 2-ethylhexyl epoxythalate, glycerol triacetate, methyl linoleate, dibutyl fumarate, methyl acetyl ricinoleate. Examples of suitable plasticizers include acetylated esters such as acetylated esters, acetyl tri(n-butyl) citrate, acetyl triethyl citrate, tri(n-butyl) citrate, triethyl citrate, bis(2-hydroxyethyl) dimerate, butyl ricinoleate, glyceryl tri(acetyl ricinoleate), methyl ricinoleate, n-butyl acetyl ricinoleate, propylene glycol ricinoleate, diethyl succinate, diisobutyl adipate, dimethyl azelate, di(n-hexyl) azelate, tributyl phosphate, and mixtures thereof. Particularly preferred plasticizers are the citrate esters.
[0071] In another preferred embodiment of the present invention, the additives are contrast agents, radiopaque markers, and radioactive materials. These additives may be incorporated into the poly(butylene succinate) or its copolymers prior to preparation of the implant, such as a fiber, mesh, or 3D print, or after preparation of the implant.
[0072] In yet another embodiment of the invention, the additive is another polymer, preferably another resorbable polymer. Other examples of resorbable polymers that can be incorporated into the compositions used to make the implants include glycolic acid, lactic acid, 1,4-dioxanone, trimethylene carbonate, ε-caprolactone, 3-hydroxybutyrate, 4-hydroxybutyrate polymers and copolymers, such as polyglycolic acid, polylactic acid, polydioxanone, polycaprolactone, poly 4-hydroxybutyrate and its copolymers, poly 3-hydroxybutyrate, copolymers of glycolic acid and lactic acid, such as VICRYL® polymers, MAXON® and MONOCRYL® polymers, such as poly(lactide-co-caprolactone), poly(orthoesters), polyanhydrides, poly(phosphazenes), synthetic or biologically prepared polyesters, polycarbonates, tyrosine polycarbonates, polyamides (including synthetic and natural polyamides, polypeptides, and poly(amino acids)), polyesteramides, poly(alkylene alkylates), polyethers (polyethylene glycols, PE Hydrophilic or water-soluble polymers including blocks of polyethylene glycol, (PEG) or polyvinylpyrrolidone (PVP), such as poly(lactide), poly(lactide-co-glycolide), polycaprolactone, polycaprolactone, polyvinylpyrrolidone or PVP, polyurethanes, polyetheresters, polyacetals, polycyanoacrylates, poly(oxyethylene) / poly(oxypropylene) copolymers, polyacetals, polyketals, polyphosphates, (phosphorus-containing) polymers, polyphosphoesters, polyalkylene oxalates, polyalkylene succinates, poly(maleic acid), silk (including recombinant silk, and silk derivatives and analogues), chitin, chitosan, modified chitosan, biocompatible polysaccharides, other biocompatible or biodegradable polymers, such as polyethylene glycol, (PEG) or polyvinylpyrrolidone (PVP), such as poly(lactide), poly(lactide-co-glycolide), or polycaprolactone and its copolymers, such as random and block copolymers thereof.
[0073] In one embodiment, the polymer composition of PBS or its copolymers is not blended with another polymer, hi another embodiment, the polymer composition of PBS or its copolymers is not blended with polylactic acid (PLA). C. Bioactive Agents
[0074] If desired, the polybutylene succinate and copolymer implants may incorporate bioactive agents, which may be incorporated during the formulation process, during pelleting or blending, or may be added to the implant at a later time.
[0075] Examples of bioactive agents that can be incorporated into the poly(butylene succinate) or copolymer implants include, but are not limited to, small molecule drugs, anti-inflammatory agents, immunomodulatory agents, molecules that promote cell migration, molecules that promote or retard cell division, molecules that promote or retard cell proliferation and differentiation, molecules that stimulate cell phenotypic modification, molecules that promote or retard angiogenesis, molecules that promote or retard angiogenesis, molecules that promote or retard extracellular matrix arrangement, signaling ligands, platelet rich plasma, peptides, proteins, glycoproteins. , anesthetics, hormones, antibodies, antibiotics, antimicrobials, growth factors, fibronectin, laminin, vitronectin, integrins, steroids, hydroxyapatite, silver particles, vitamins, nonsteroidal anti-inflammatory drugs, chitosan and its derivatives, alginate and its derivatives, collagen, sugars, polysaccharides, nucleotides, oligonucleotides, lipids, lipoproteins, anti-adhesion agents, hyaluronic acid and its derivatives, allograft materials, xenograft materials, ceramics, nucleic acid molecules, antisense molecules, aptamers, siRNA, nucleic acids, and combinations thereof. In a particularly preferred embodiment, an implant designed to allow tissue ingrowth on one surface of the implant and prevent tissue ingrowth on another surface can be coated with Sepra® hydrogel barrier on the surfaces where tissue ingrowth is undesirable. Such implants can be used to minimize tissue adhesion to the visceral side of the implant after intraabdominal placement, for example in hernia repair.
[0076] Antimicrobial agents that can be incorporated into the poly(butylene succinate) and copolymer implants include, but are not limited to, antibacterial drugs, antiviral drugs, antifungal drugs, and antiparasitic drugs. Antimicrobial agents include substances that kill or inhibit the growth of microorganisms, such as microbicides and microbistatics. Antimicrobial agents that can be incorporated into the poly(butylene succinate) and copolymer implants include, but are not limited to, rifampin, minocycline and its hydrochloride, sulfate, or phosphate salts, triclosan, chlorhexidine, vancomycin and its hydrochloride, sulfate, or phosphate salts, tetracycline and its hydrochloride, sulfate, or phosphate salts and derivatives, gentamicin, cephalosporin antimicrobials, aztreonam, cefotetan and its disodium salt, loracarbef, cefoxitin and its sodium salt, cefazolin and its sodium salt, cefaclor, ceftibuten and its sodium salt, ceftizoxime, ceftizoxime sodium salt, cefoperazone and its sodium salt, cefuroxime and its sodium salt, cefuroxime axetil, cefprozil, ceftazidime, cefotaxime and its sodium salt, cefadroxil, ceftazidime and its sodium salt, cephalexin, cefamandole nafate, cefepime and its hydrochloride, sulfate, and phosphate salts, cefdinir and its sodium salt, ceftriaxone and its sodium salt cefixime and its sodium salt, cefpodoxime proxetil, meropenem and its sodium salt, imipenem and its sodium salt, cilastatin and its sodium salt, azithromycin, clarithromycin, dirithromycin, erythromycin and its hydrochloride, sulfate, or phosphate salts, ethylsuccinate and its stearate forms, clindamycin, clindamycin hydrochloride, sulfate, or phosphate salts, lincomycin and its hydrochloride, sulfate, or phosphate salts, tobramycin and its hydrochloride, sulfate, or or phosphate, streptomycin and its hydrochloride, sulfate, or phosphate, neomycin and its hydrochloride, sulfate, or phosphate, acetylsulfisoxazole, colistimethate and its sodium salt, quinupristin, dalfopristin, amoxicillin, ampicillin and its sodium salt, clavulanic acid and its sodium or potassium salt, penicillin G, penicillin G benzathine or procaine salt, penicillin G sodium or potassium salt, carbenicillin and its disodium salt or indanyl dihydrochloride ... thorium salts, piperacillin and its sodium salt, ticarcillin and its disodium salt, sulbactam and its sodium salt, moxifloxacin, ciprofloxacin, ofloxacin, levofloxacin, norfloxacin, gatifloxacin, trovafloxacin mesylate, alatrofloxacin mesylate, trimethoprim, sulfamethoxazole, demeclocycline and its hydrochloride, sulfate, or phosphate salts, doxycycline and its hydrochloride, sulfate, or phosphate salts, oxytetracycline and its hydrochloride, sulfate,or phosphate, chlortetracycline and its hydrochloride, sulfate, or phosphate salts, metronidazole, dapsone, atovaquone, rifabutin, linezolid, polymyxin B and its hydrochloride, sulfate, or phosphate salts, sulfacetamide and its sodium salt, clarithromycin, and silver ions, salts, and complexes. In a preferred embodiment, the antimicrobial agents incorporated into the implant are (i) rifampin and (ii) minocycline and its hydrochloride, sulfate, or phosphate salts. In a particularly preferred embodiment, the poly(butylene succinate) and copolymers thereof implant comprises rifampin and minocycline or its hydrochloride, sulfate, or phosphate salts. III. Methods for synthesizing and processing poly(butylene succinate) and copolymer implants A. Poly(butylene succinate) and its copolymers
[0077] Poly(butylene succinate) and its copolymers can be synthesized by any suitable method. The suitable method must provide a biocompatible polymeric composition of PBS and its copolymers. In one embodiment, poly(butylene succinate) can be synthesized by (i) esterification of succinic acid with 1,4-butanediol or transesterification of dimethyl succinate with 1,4-butanediol to obtain oligomers, and (ii) polycondensation of the oligomers to form poly(butylene succinate) with high weight average molecular weight.
[0078] In one method, poly(butylene succinate) can be prepared by charging a suitable vessel with succinic acid (or dimethyl succinate) in a 1:1 ratio (or with a small excess of 1,4-butanediol). The reactants are heated under an inert atmosphere to 130-190°C, more preferably 160-190°C, to melt the acid components and distill off the water (or methanol). Once distillation is complete, high vacuum is used to reduce pressure within the vessel. Then, in the presence of a catalyst, polycondensation is carried out at a temperature of preferably 220 to 240° C. to produce poly(butylene succinate) having a suitable high weight average molecular weight.
[0079] Suitable catalysts for the synthesis of poly(butylene succinate) include p-toluenesulfonic acid, tin(II) chloride, monobutyltin oxide, tetrabutyl titanate, tetraisopropyl titanate, lanthanide triflates, and distannoxanes. The catalyst may contain metal elements from groups 1 to 14 of the periodic table. Preferred catalysts have metal elements of scandium, yttrium, titanium, zirconium, vanadium, molybdenum, tungsten, zinc, iron, and germanium. Titanium and zirconium catalysts are particularly preferred for the preparation of poly(butylene succinate) and its copolymers. Tetraalkyl titanates are preferred catalysts. Specifically, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof are preferred.Furthermore, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, titanium (diisopropoxide) acetylacetonate, titanium bis(ammonium lactate) dihydroxide, titanium bis(ethylacetoacetate) diisopropoxide, titanium (triethanolamine) isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolamine, and butyl titanate dimer are also preferred catalysts. Among these, tetra-n-propyl titanate, tetraisopropyl titanate, and tetra-n-butyl titanate, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxy titanium stearate, titanium lactate, and butyl titanate dimer are preferred, and tetra-n-butyl titanate, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, polyhydroxy titanium stearate, titanium lactate, and butyl titanate dimer are more preferred. In particular, tetra-n-butyl titanate, polyhydroxy titanium stearate, titanium (oxy) acetylacetonate, and titanium tetraacetylacetonate are preferred.Zirconium catalysts which may be used to prepare the polymer or copolymer include zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, zirconium potassium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof. Among these, zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, zirconium ammonium oxalate, zirconium potassium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide are preferred, and zirconyl diacetate, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconium ammonium oxalate, zirconium tetra-n-propoxide, and zirconium tetra-n-butoxide are more preferred. In particular, zirconium tris(butoxy)stearate is preferred. The germanium catalyst that can be used includes inorganic germanium compounds such as germanium oxide and germanium chloride, and organic germanium compounds such as tetraalkoxy germanium. Preferred are germanium oxide, tetraethoxygermanium, tetrabutoxygermanium, etc. Other metal-containing catalysts which may be used include scandium compounds such as scandium carbonate, scandium acetate, scandium chloride, and scandium acetylacetonate, yttrium carbonate, yttrium chloride, etc. Included are yttrium compounds such as yttrium acetate and yttrium acetylacetonate; vanadium compounds such as vanadium chloride, vanadium oxide trichloride, vanadium acetylacetonate and vanadium acetylacetonate oxide; molybdenum compounds such as molybdenum chloride and molybdenum acetate; tungsten compounds such as tungsten chloride, tungsten acetate and tungstic acid; and lanthanide compounds such as cerium chloride, samarium chloride and ytterbium chloride.
[0080] When a metal compound is used as the catalyst, the amount of catalyst used to prepare the poly(butylene succinate) or copolymer thereof is preferably 0.1 ppm or more, preferably 0.5 ppm or more, more preferably 1 ppm or more, and less than 30,000 ppm, preferably less than 1,000 ppm, more preferably less than 250 ppm, more preferably less than 130 ppm.
[0081] After polycondensation is complete, the polymer can be purified by dissolving in a solvent, filtering, and precipitating. For example, the polymer can be dissolved in chloroform, filtered, and precipitated with an alcohol such as methanol or ethanol. If desired, the polymer can be further purified, for example, by washing with diethyl ether. Preferably, the amount of metal in the poly(butylene succinate) or copolymer thereof is less than 100 ppm, more preferably less than 50 ppm. The preferred metal content in the poly(butylene succinate) or copolymer thereof is 0.1-100 ppm, more preferably 1-50 ppm.
[0082] In one embodiment, the polymer composition of PBS and its copolymers used to prepare the implant contains 1-500 ppm of one or more of the following: silicon, titanium, and zinc. Preferably, the polymer composition contains less than 50 ppm of silicon, titanium, and zinc. In another embodiment, the polymer composition used to make the implant does not contain any metal other than silicon, titanium, and zinc in an amount detectable by PIXE analysis. In a particularly preferred embodiment, the polymer composition used to make the implant does not contain tin.
[0083] Copolymers of poly(butylene succinate) may be formed by copolymerization with various comonomer units, preferably dicarboxylic acids and diols, such as adipic acid, terephthalic acid, fumaric acid, ethylene glycol, and 1,3-propanediol. Other suitable diol and dicarboxylic acid comonomer units include 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,2-pentanediol, 2,4-pentanediol, 1,6-hexanediol, 1,2-hexanediol, suberic acid, sebacic acid, azelaic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, and octadecanedicarboxylic acid. In a preferred embodiment, the content of comonomer units is less than 30%, more preferably less than 20%, and even more preferably less than 15%. In another preferred embodiment, the comonomer content in the copolymer is less than 15%, and the melting point of the comonomer is greater than 100°C. Preferably, the melting point of the PBS copolymer is from 105°C to 120°C.
[0084] In yet another embodiment, the polymers and copolymers of succinic acid and 1,4-butanediol may contain chain branches, most preferably chain branches formed with aliphatic oxycarboxylic acids. Preferred chain branching agents are trifunctional and tetrafunctional aliphatic oxycarboxylic acids. Preferred trifunctional oxycarboxylic acid chain branching agents may have (i) two carboxyl groups and one hydroxyl group in the same molecule (such as malic acid) or (ii) one carboxyl group and two hydroxyl groups in the same molecule. Preferred tetrafunctional oxycarboxylic acid chain branching agents may have (i) three carboxyl groups and one hydroxyl group in the same molecule (such as citric acid), (ii) two carboxyl groups and two hydroxyl groups in the same molecule (such as tartaric acid), or (i ii) may have three hydroxyl groups and one carboxyl group in the same molecule. Other chain branching agents that may be incorporated include hydroxyglutaric acid, hydroxymethylglutaric acid, hydroxyisophthalic acid, and hydroxyterephthalic acid. Malic acid, tartaric acid, and citric acid are particularly preferred chain branching agents. Chain branching agents, crosslinking agents, coupling agents, and chain extenders are preferably incorporated into the poly(butylene succinate) and its copolymers in an amount of 0.01-5.0 mol%, more preferably 0.01-2.5 mol%, and most preferably 0.1-0.5 mol%. In one embodiment, the chain branching agent is malic acid. In a preferred embodiment, malic acid is incorporated into the poly(butylene succinate) polymer or copolymer in an amount of 0.01-5.0 mol%, more preferably 0.1-0.5 mol%, or in an amount of 0.01-1 part by weight, more preferably 0.1-0.5 parts by weight. When malic acid is used as the trifunctional oxycarboxylic acid acting as a copolymerizable component, examples of copolyesters include succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-malic acid-tartaric acid copolyester, succinic acid-adipic acid-1,4-butanediol-malic acid-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid-citric acid copolyester, and succinic acid-adipic acid-1,4-butanediol-malic acid-citric acid copolyester. Malic acid may exist as the L-enantiomer, the D-enantiomer, or both, with L-malic acid being preferred. During exposure to heat or further processing, the malic acid monomer in the copolymer may dehydrate to produce fumaric acid and maleic acid monomers in the copolymer. Thus, the implants disclosed herein may contain fumaric and maleic acid units, or a combination thereof. B. Spinning of Poly(butylene succinate) and its Copolymers
[0085] Poly(butylene succinate) and its copolymers can be processed and oriented to provide implants with high tensile strength and long term strength retention. The polymers may be melt or solution processed. In one preferred embodiment, poly(butylene succinate) and its copolymers are melt processed.
[0086] In melt processing of poly(butylene succinate) and its copolymers, it is important to prevent hydrolysis of the polymer due to residual moisture. Therefore, it is important to dry the polymer before melt processing. In a preferred embodiment, the poly(butylene succinate) and copolymers are dried before melt processing, so that they have a moisture content of less than 0.1 wt%, preferably less than 0.05 wt%, more preferably less than 0.01 wt%, even more preferably less than 0.005 wt%. The polymer may be dried under hot air and vacuum before melt processing. In a preferred embodiment, the polymer is dried under vacuum at 30-90°C, more preferably 60-90°C.
[0087] To obtain implants with high tensile strength and long-term strength retention, it is important to prevent loss of weight average molecular weight during melt processing of poly(butylene succinate) and its copolymers. At temperatures above 200°C, the shear viscosity of poly(butylene succinate) can decrease significantly. The extent of loss increases as the temperature increases above 200°C and the exposure time increases. Therefore, to create implants with the highest tensile strength and long-term strength retention, it is important to minimize the time the polymer is exposed to high processing temperatures, as well as the presence of moisture in the polymer. In one embodiment, the implant is melt extruded with a temperature profile of 60-230°C, more preferably 80-180°C, and even more preferably 80-170°C.
[0088] Examples 1 and 2 described herein compare two different methods of melt extruding poly(butylene succinate) and its copolymers. It has been discovered that the method results in fibers having substantially higher tensile strengths than those obtained by the method described in Example 1. Thus, when it is desired that the fibers have high tensile strength and long term strength retention, the method disclosed in Example 2 is preferred for making implants containing the fibers. Using the method disclosed in Example 2, fibers having tensile strengths of 779-883 MPa were obtained, compared to tensile strengths of 434-518 MPa produced by the method disclosed in Example 1. In contrast to the method of Example 1, the use of multiple incremental fiber orientations, as well as the use of a conductive chamber instead of the standard conventional chamber used in Example 1, resulted in fibers having surprisingly high tensile strengths. In a preferred embodiment, monofilament or multifilament fibers comprising poly(butylene succinate) and its copolymers are produced by a process comprising the steps of: (a) spinning a multifilament or monofilament fiber comprising the polymer composition; (b) drawing the multifilament or monofilament fiber in one or more stages at an orientation ratio of at least 3.5 and at a temperature of 50-70°C; (c) drawing the multifilament or monofilament fiber in one or more stages at an orientation ratio of at least 2.0 and at a temperature of 65-75°C; and (d) drawing the multifilament or monofilament fiber in one or more stages at an orientation ratio of greater than 1.0 and at a temperature of 70-75°C. Preferably, the sum of the orientation ratios is greater than 6.0, 6.5, 7.0, 7.5, or 8.0. In an even more preferred embodiment, the fiber is drawn in a conductive liquid chamber. Prior to drawing the fiber, the melt extruded polymer is preferably quenched in a conductive liquid bath. The temperature of the bath is preferably between 50°C and 70°C. Further cooling of the fiber after quenching is desirable, which is accomplished by passing the fiber between two godets. In one embodiment, the temperature range for extrusion of PBS or its copolymers to form high strength fibers is 60-230°C, or 75-220°C, but more preferably 75-200°C, 80-180°C, 80-175°C, or 80-170°C.Example 3 discloses a specific example of the method using multiple incremental orientation steps and the use of a conductive chamber to prepare multifilament fibers of PBS and its copolymers. Examples of multifilament fibers with tensile strengths of 8.3 to 12.5 g / d are shown.
[0089] If desired, the oriented fibers may be annealed. In one embodiment, the oriented fibers may be annealed using a temperature between 80°C and 120°C, more preferably 105°C ± 10°C.
[0090] In one embodiment, the oriented monofilament fibers have a diameter in the range of 0.01 to 1.00 mm. In a particularly preferred embodiment, the monofilament fibers have a diameter in the range of 0.07 to 0.7 mm. In another embodiment, the monofilament fibers optionally meet USP standards for absorbable monofilament sutures.
[0091] In one embodiment, monofilament fibers of PBS and its copolymers have a tensile strength of 400 MPa to 2,000 MPa, more preferably greater than 500 MPa, 600 MPa, 700 MPa, or 800 MPa, but less than 1,200 MPa. In another embodiment, monofilament fibers of PBS and its copolymers have a Young's modulus of at least 600 MPa and less than 3 GPa, but more preferably greater than 800 MPa, 1 GPa, 1.5 GPa, and 2 GPa. In a further embodiment, monofilament fibers of PBS and its copolymers have an elongation at break of 10 to 150%, more preferably 10 to 50%.
[0092] In yet another embodiment, the multifilament fibers of PBS and its copolymers have a tensile strength greater than 4 g / denier but less than 14 g / denier. Preferably, the multifilament fibers have an elongation at break of 15% to 50%.
[0093] Poly(butylene succinate) and its copolymer yarns and monofilament fibers can be used to prepare knitted and woven meshes, nonwoven meshes, suture tapes, mesh sutures, webs, and patches. These mesh, web, and patch products are particularly useful for soft tissue repair, hernia repair, breast augmentation, breast reconstruction, face and neck augmentation, pelvic floor reconstruction, stress urinary incontinence treatment, organ retrieval, elevation and suspension procedures, and for making housings, pouches, holders, covers, collapsible containers, and casings to hold implantable medical devices.
[0094] In view of their mechanical properties, the yarns and monofilament fibers disclosed herein are suitable for use as sutures, braided sutures, hybrid sutures of monofilament and multifilament fibers, barbed sutures, suture tapes, mesh sutures, braids, ligatures, tapes, knitted or woven meshes, knitted tubes, multifilament meshes, patches, wound healing devices, bandages, wound dressings, burn dressings, ulcer dressings, skin replacements, hemostatic materials, tracheal reconstruction devices, organ retrieval devices, dural replacements, dural patches, nerve regeneration or repair devices, hernia repair devices, and the like. repair devices, hernia meshes, hernia plugs, devices for temporary wound or tissue support, scaffolds for tissue engineering, guided tissue repair / regeneration devices, anti-adhesion membranes, adhesion barriers, tissue isolation membranes, retention membranes, slings, devices for pelvic floor reconstruction, urethral suspension devices, devices for the treatment of urinary incontinence, devices for the treatment of vesicoureteral reflux, bladder repair devices, devices for sphincter repair, suture anchors, soft tissue anchors, bone anchors, ligament repair devices, ligament strengthening devices, ligament grafts, anterior cruciate ligament repair devices, tendon repair devices, tendon grafts, tendon strengthening devices vices, rotator cuff repair devices, meniscus repair devices, meniscus regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, stents, including coronary, cardiovascular, peripheral, ureteral, urethral, urological, gastrointestinal, nasal, ophthalmic, or neurological stents, stent grafts, cardiovascular patches, vascular closure devices, intracardiac septal defect repair devices, including, but not limited to, atrial septal defect repair devices and PFO (patent foramen ovale) closure devices, left atrial appendage (LAA) closure devices, pericardial patches, venous valves, heart valves, vascular grafts, myocardial regeneration devices , periodontal meshes, guided tissue regeneration membranes for periodontal tissue, embolization devices, anastomosis devices, devices for cell seeding, devices for controlled release, devices for drug delivery, plastic surgery devices, devices for breast lift, devices for mastopexy, devices for breast reconstruction, devices for breast augmentation (including devices for use with breast implants), devices for breast reduction (including devices for the removal, reshaping and reorientation of breast tissue), devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift,They may also be used to prepare medical devices including eyelid lift devices, face lift devices, wrinkle removal devices, thread lift devices (for lifting and supporting sagging areas of the face, eyebrows, and neck), rhinoplasty devices, cheekbone augmentation devices, earplasty devices, neck lift devices, chinplasty devices, buttock lift devices, cosmetic repair devices, devices for facial scar correction, as well as housings, pouches, holders, covers, foldable containers, casings for holding implantable medical devices. C. 3D Printing of Implants
[0095] In another preferred embodiment, the implant may be prepared by 3D printing. Methods that can be used to 3D print poly(butylene succinate) and its copolymers include fused filament fabrication (FFF), fused pellet deposition, melt extrusion deposition (MED), selective laser melting, and solution printing.
[0096] A particularly preferred method for 3D printing poly(butylene succinate) and its copolymers is to feed the polymer or copolymer filaments into an FFF printer. In the FFF of poly(butylene succinate) and its copolymers, it is important to prevent hydrolysis of the polymer due to residual moisture. Therefore, the filaments used for FFF are It is important that the filaments have a low moisture content, preferably less than 0.1 wt%, preferably less than 0.05 wt%, more preferably less than 0.01 wt%, even more preferably less than 0.005 wt%. The filaments may be dried under hot air and vacuum prior to printing. In a preferred embodiment, the polymer is dried under vacuum at 30-90°C, more preferably 60-90°C.
[0097] To obtain 3D printed implants with high tensile strength and long-term strength retention, it is important to prevent the loss of weight average molecular weight during melt processing of poly(butylene succinate) and its copolymers. As the temperature increases above 200°C and the exposure time increases, the degree of molecular weight loss increases. Therefore, to create implants with the highest tensile strength and long-term strength retention, it is important to minimize the time the polymer is exposed to high processing temperatures during 3D printing, as well as the presence of moisture in the polymer or copolymer. The temperature of the heating end, including the nozzle of the printer, may be set to a temperature in the range of 120°C to 300°C, more preferably 130°C to 230°C, and even more preferably 150°C to 200°C.
[0098] Methods for 3D printing of PBS and its copolymers are shown in Example 9 and Example 10. 3D printing of PBS-malic acid copolymers by MED using various thermal conditions is shown in Example 18, and the properties of the resulting implants are shown in Table 17. Surprisingly, it was found that the weight average molecular weight of the PBS polymer increases with increasing processing temperature from 180° C. to 220° C. (at 230° C., the weight average molecular weight decreased from the peak at 220° C.). The increase in molecular weight is particularly advantageous in some implant applications. For example, an increase in the weight average molecular weight may result in long-term strength retention of the implant. In one embodiment, an implant is produced that includes PBS and its copolymers having a weight average molecular weight that exceeds the weight average molecular weight of the composition used to prepare the implant. The implants are formed by 3D printing including fused filament fabrication, fused pellet deposition, melt extrusion deposition, and selective laser melting, but may also be formed using other thermal processing techniques such as melt processing, melt extrusion, melt blowing, melt spinning, injection molding, compression molding, lamination, foaming, film extrusion, thermoforming, pultrusion, molding, tube extrusion, spunbonding, nonwoven fabric manufacturing, etc. In one embodiment, implants comprising PBS and copolymers thereof can be formed by melt processing with a weight average molecular weight 1-50%, more preferably 5-30% higher than the weight average molecular weight of the PBS and copolymer resins used to prepare the implant. D. Other methods of manufacturing implants
[0099] Implants comprising poly(butylene succinate) and its copolymers can be fabricated using a variety of techniques including casting, solvent casting, solution spinning, solution bonding of fibers, melt processing, extrusion, melt extrusion, melt spinning, fiber spinning, orientation, relaxation, annealing, injection molding, compression molding, lamination, particle formation, formation of microparticles, large particles and nanoparticles, foaming, dry spinning, knitting, weaving, crocheting, melt blowing, film formation, film blowing, film casting, membrane formation, electrospinning, thermoforming, pultrusion, centrifugal spinning, molding, tube extrusion, spunbonding, nonwoven fabric manufacturing, staple fiber entanglement, fiber knitting, weaving and crocheting, mesh manufacturing, coating, dip coating, laser cutting, barb formation, fiber barb formation, punching, perforation, hole formation, lyophilization, stitching, calendaring, freeze-drying, phase separation, particle leaching, thermal phase separation, leaching, latex processing, gas plasma processing, etc. They may be prepared by polymer processing, emulsion processing, 3D printing, fused filament manufacturing, fused pellet deposition, melt extrusion deposition, selective laser melting, printing of slurries and solutions using coagulation baths, and printing using binding solutions and powder granules. E. Antimicrobial Coatings
[0100] In one embodiment, implants comprising poly(butylene succinate) and its copolymers may be coated with a solution of antimicrobial agent dissolved in a poor solvent for poly(butylene succinate) and its copolymers. These poor solvents do not cause significant, if any, loss of orientation of poly(butylene succinate) or its copolymers. However, these poor solvents allow the antimicrobial agent to soften slightly and penetrate the surface of the implant. This has two main advantages. First, it allows the implant to be coated with a higher concentration of antimicrobial agent, and second, it allows the antimicrobial agent to diffuse into the implant. The diffusion of the antimicrobial agent into the implant provides a longer release profile and increases the ability of the implant to prevent colonization of the implant, reducing or preventing the occurrence of infection after implantation in a patient. A suitable poor solvent that can dissolve the antimicrobial agent but does not cause loss of orientation of the implant is an aqueous or alcoholic solution of tetrahydrofuran (THF). Alcohols that can be combined with this solvent include methanol and ethanol. The concentration of the antimicrobial agent in the poor solvent may range from about 0.1 mg / mL to about 100 mg / mL, preferably from about 1 mg / mL to about 30 mg / mL. The amount of each antimicrobial agent coated on the implant (cover density) is about 1 μg / cm 2 ~Approx. 1000μg / cm 2 , preferably about 50 μg / cm 2 ~Approx. 200μg / cm 2 In various embodiments, the amount may range from about 10 μg / cm 2 ~Approx. 175μg / cm 2 , about 10μg / cm 2 ~Approx. 150μg / cm 2 , about 10μg / cm 2 ~Approx. 100μg / cm 2 , about 10μg / cm 2 ~Approx. 75μg / cm 2 , about 20μg / cm 2 ~Approx. 200μg / cm 2 , about 50μg / cm 2~Approx. 200μg / cm 2 , about 75μg / cm 2 ~Approx. 200μg / cm 2 , about 100μg / cm 2 ~Approx. 200μg / cm 2 , about 150μg / cm 2 ~Approx. 200μg / cm 2 The range is.
[0101] In a preferred embodiment of the present invention, poly(butylene succinate) and copolymer implants are coated with rifampin and minocycline (including their hydrochloride, sulfate, or phosphate salts) dissolved in antisolvents for poly(butylene succinate) and copolymers. The antimicrobial agents may be applied to the oriented implants individually using the same or different antisolvents, or from a single solution containing both antimicrobial agents in an antisolvent. In one embodiment, rifampin may be applied to poly(butylene succinate) and copolymer implants from a solution of the following antisolvents: (i) THF, (ii) DMSO, (iii) DMF, and (iv) DMA, each mixed with one or more of the following: water, methanol, and / or ethanol. In another embodiment, minocycline may be applied to oriented poly(butylene succinate) and copolymer implants from a solution of the following antisolvents: THF / water, THF / methanol, and THF / ethanol. In a preferred embodiment, rifampin and minocycline (including their hydrochloride, sulfate, or phosphate salt forms) are applied to the implant dissolved in a solution of THF / water, THF / ethanol, or THF / ethanol. F. Sterilization of Implants
[0102] Implants made from high tensile strength yarns and monofilament fibers of poly(butylene succinate) and its copolymers, or other implants of poly(butylene succinate) and its copolymers, can be sterilized using ethylene oxide gas, and even more preferably, cold cycle ethylene oxide. In another preferred embodiment, the implants can be sterilized by electron beam or gamma irradiation. In another embodiment, the implants can be sterilized using alcohol. The sterility of the device can be maintained by packaging the device in packaging designed to protect the device from contamination and maintain sterility. IV. Poly(butylene succinate) and its copolymers implants
[0103] The poly(butylene succinate) and copolymer compositions described herein are suitable for the preparation of implants for the repair, regeneration, and replacement of soft and hard tissues.
[0104] Oriented forms of poly(butylene succinate) and its copolymers are particularly suitable for use in applications that require long-term strength retention. The multifilament yarns and monofilament fibers disclosed herein have long-term strength in vivo, making them suitable for soft tissue repair that requires high strength and requires long-term strength maintenance. Other examples of applications for high-strength yarns and monofilament fibers include soft and hard tissue repair, replacement, remodeling, and reconstruction, including wound closure; breast lift, including breast reconstruction and mastopexy; face lifts, such as face lifts, neck lifts, and eyebrow lifts; ligament and other tendon repairs; abdominal closures; hernia repairs; anastomoses; slings for tissue lifts; slings for stress urinary incontinence treatment; and pelvic floor reconstruction. A. Sutures and braids
[0105] As shown in Example 16 and Example 15, it has been discovered that oriented fibers of PBS and its copolymers have long-term strength retention when implanted in vivo. Figure 5 is an SEM of oriented fibers removed after 4 weeks. Surprisingly, the surface of the fiber shows little, if any, noticeable surface pitting or localized surface erosion at 400x magnification. This result is surprising in light of the known surface erosion and pitting of fibers derived from other resorbable fibers. This discovery allows the use of the fibers in applications where long-term strength retention is required. The absence of surface erosion is particularly important in the strength retention of small diameter fibers, where pitting of the fiber surface can rapidly reduce strength retention. The fibers are also useful in applications where high initial tensile strength is required. Example 16 clearly shows that the oriented fibers do not lose a significant amount of tensile strength in the first 4 weeks when implanted in vivo. The studies described in Example 15 further demonstrate that meshes made from oriented fibers of PBS or its copolymers retained 74.1% of their strength after 12 weeks, indicating long-term strength retention of the fibers. Analysis of the weight average molecular weight of the embedded fibers in these studies after 4 and 12 weeks indicates that the fibers are degrading. The weight average molecular weight of the suture fibers in Example 16 decreases from 7.3% to 92.7% of the initial value at 4 weeks, and the weight average molecular weight of the fibers in the mesh decreases from 25.9% to 74.1% of the initial value at 12 weeks. The in oriented fibers of PBS and its copolymers shown in Example 12 It is also clear that there is a good correlation between the in vitro weight average molecular weight loss and the in vivo data shown in Examples 15 and 16. This good correlation is further evidence that oriented fibers resist surface pitting or surface erosion.
[0106] In a preferred embodiment, the weight average molecular weight of the fibers of PBS or copolymers thereof is reduced by 3-15% over a 4 week period in vivo, 5%-15% over an 8 week period, or 10-35%, more preferably 10-30%, over a 12 week period in vivo under physiological conditions. The percentage mass loss of the fibers is preferably 0%-5% over a 4 week period in vivo under physiological conditions.
[0107] In one embodiment, the monofilament fibers used to prepare the sutures, suture meshes, braids, and tapes have a tensile strength of 400 MPa to 2,000 MPa, more preferably greater than 500 MPa, 600 MPa, 700 MPa, or 800 MPa and less than 1,200 MPa. Preferably, the monofilament fibers used to prepare the sutures, suture meshes, and tapes have a Young's modulus of 600 MPa to 3 GPa, but preferably at least 800 MPa, 1 GPa, or 2 GPa. A high Young's modulus of fiber can reduce the suture's tendency to become pig-tailed or to become creased during suturing. It has been found that the formation of pores is prevented. In another preferred embodiment, the monofilament fibers used to prepare the sutures, suture meshes, braids, and tapes have a melting temperature above 100°C, preferably between 105°C and 120°C.
[0108] Monofilament fibers of poly(butylene succinate) and its copolymers can also be used to prepare high strength monofilament sutures, hybrid sutures of monofilament and multifilament fibers that have good trackability, high knot strength, and can be tied securely with low profile knot bundles (i.e., can be secured by tying several times). In one embodiment, the monofilament fibers can be fabricated into resorbable, high strength sutures and suture anchors that can be used, for example, in rotator cuff repair. These sutures and anchors are particularly useful in plastic surgery procedures such as shoulder, elbow, wrist, hand, hip, knee, ankle, and foot repair, including tendon and ligament repair, and lifts and suspensions, including soft tissue access, soft tissue ligation, abdominal closure, and face and breast lifts and breast reconstruction. Monofilament sutures and suture anchors (including soft tissue anchors) may incorporate one or more needles and may be clear or dyed, if desired, braided as part of the suture or suture anchor or braided as a flat tape.
[0109] Monofilament fibers of poly(butylene succinate) and its copolymers may also be used to prepare barbed sutures.
[0110] Multifilament fibers of poly(butylene succinate) and its copolymers can be used to prepare high strength multifilament sutures, hybrid sutures of monofilament and multifilament fibers that have excellent conformability, long term strength retention, high knot strength, good drapeability, and can form low profile flexible knot bundles to be tied securely. Example 3 discloses one method that can be used to make high strength multifilaments of PBS or its copolymers suitable for use in these applications.
[0111] Multifilament yarns of PBS and its copolymers can be fabricated into resorbable, high strength sutures and suture anchors that can be used in rotator cuff repair procedures. Currently, these procedures are repaired using permanent sutures because existing resorbable sutures degrade too quickly. In contrast to existing resorbable sutures, sutures prepared using the high tensile strength yarns of the present invention not only provide high initial strength that stabilizes the repair under significant loads, but also allow for soft tissue repair by slowly losing strength. High strength sutures can also be used for bone anchors, suture anchors, and soft tissue anchors. These sutures and anchors are particularly useful in shoulder, elbow, wrist, hand, hip, knee, ankle, and foot repairs, including tendon and ligament repairs, as well as elevation and suspension procedures. Bone anchors, suture anchors, and soft tissue anchors may incorporate one or more needles, yarns of various colors, and flat braided sections if desired. The ability to use resorbable, high tensile strength sutures, suture anchors, bone anchors, and soft tissue anchors for procedures such as rotator cuff repair eliminates long term complications that can result from foreign bodies such as permanent sutures. These sutures can be used, for example, for soft tissue access, anastomosis, suspension and elevation procedures, and other applications in plastic surgery.
[0112] In one preferred embodiment, yarns of poly(butylene succinate) and its copolymers can be used to prepare high strength braided sutures, with suture failure loads ranging from 40 N to 270 N. In a particularly preferred embodiment, high tensile strength braided sutures comprising poly(butylene succinate) and its copolymers have at least 40% strength retention at 4-6 months after implantation in vivo under physiological conditions.
[0113] The suture braid can be made from United States Pharmacopeia (USP) suture sizes 12-0, 11-0, 10-0, 9-0, 8-0, 7-0, 6-0, 5-0, 4-0, 3-0, 2-0, 0, 1, 2, 3, 4, and 5 yarns and meet the USP knot-tie tensile strength or breaking load for these sizes. In another embodiment, the suture braid can be oversized in diameter to meet the USP knot-tie tensile strength or breaking load. For example, the diameter of the suture braid can be oversized by up to 0.3 mm, preferably 0.2 mm, more preferably 0.1, and even more preferably 0.05 mm. The suture can be needled and / or include a loop at either end.
[0114] In another embodiment, the yarns of poly(butylene succinate) and its copolymers and the monofilaments of poly(butylene succinate) and its copolymers can be used to prepare flat suture tapes, including flat braided suture tapes. These suture tapes are useful for accessing and / or ligating soft tissues, and are particularly useful in procedures requiring extensive compression and increased cut resistance. For example, the suture tapes can be used in shoulder and rotator cuff repairs, such as acromioclavicular repairs, and for restoring labrum height in instability repairs, as well as ACL and PCL repairs. The suture tapes can have flat ends, tapered ends, needles at one or both ends of the suture tape, and can include yarns containing one or more different dyes.
[0115] The suture tapes disclosed herein may be used as slings for tissue support, including slings for the treatment of stress urinary incontinence.
[0116] In another embodiment, coatings may be applied to increase the lubricity of the braided suture or other fiber-based implant. These coatings include waxes, natural and synthetic polymers such as polyvinyl alcohol, and spin finishes including polyethylene glycol sorbitan monolaurate, as well as polymers or oligomers of ethylene oxide, propylene oxide, PEG400, PEG40 stearate, Dacospin, and Filapan. These coatings are preferably applied such that the braided suture has a coating weight of less than 6 wt%, more preferably less than 3 wt%, and even more preferably less than 2 wt%. The coatings preferably readily detach from the surface of the braided suture or fiber-based device in vivo, for example by decomposition or dissolution (e.g., if the coating is water-soluble).
[0117] In another embodiment, a coating may be applied to the surface of the suture to slow degradation and increase strength retention in vivo. For example, the suture may be coated with another polymer, preferably a slowly degrading polymer or composition, or may be coated with a wax. For example, the suture may be coated with polycaprolactone to slow degradation and further prolong strength retention.
[0118] Braids (including suture tapes and suture braids) made from high tensile strength yarns of poly(butylene succinate) and its copolymers are preferably prepared by coating the yarn with a spin finish, twisting or plying the yarn, and winding it onto a bobbin. A preferred spin finish is polyethylene glycol sorbitan monolaurate and polyethylene glycol. The bobbin is then placed on a braider. If desired, the number of picks per inch may be increased to improve the definition of the braid. The number of picks per inch may range from 5 to 100, preferably 30 to 60. In some embodiments, a core of monofilament, yarn, or layered yarn strands may be incorporated into the center of the braid. Alternatively, the braid may be spun into a spun yarn to produce, for example, a hollow braid. The core may be prepared without a core.
[0119] In one embodiment, yarns and monofilament fibers of poly(butylene succinate) and its copolymers can be used to prepare mesh sutures that can spread the load applied to the reapposed tissues, thereby reducing suture pull-out (the wire cutting effect of cheese) and wound dehiscence. The mesh sutures are sewn through the tissues, the mesh is secured to the tissues under tension to reappose the soft tissues, and the needles are removed. The use of mesh instead of suture fibers to reappose the tissues increases the strength of the repair. The porosity of the mesh is designed to allow tissue ingrowth into the mesh.
[0120] The mesh suture comprises a suture needle and a mesh component. The mesh component comprises fibers of poly(butylene succinate) and copolymers as described herein, preferably monofilament fibers of poly(butylene succinate) and its copolymers. The mesh component is an interwoven structure of fibers, preferably monofilament fibers of poly(butylene succinate) and its copolymers. Preferably, the mesh structure is formed by knitting, braiding, and weaving fibers comprising poly(butylene succinate) and its copolymers, most preferably monofilament fibers. The cross section of the mesh component may be elliptical, semi-elliptical, circular, semicircular, convex, rectangular, square, crescent, pentagonal, hexagonal, concave ribbon, convex ribbon, H-beam, I-beam, or dumbbell-shaped. Alternatively, the mesh component may assume these shapes as it passes through tissue. Preferably, the mesh component flattens as it passes through tissue. The mesh component may have a cross-sectional profile that varies over the length of the mesh. For example, a portion of the cross section of the mesh may be tubular and another portion may be non-tubular. However, in a preferred embodiment, the mesh has the same cross section as the suture needle, and more preferably has a cross section with dimensions not exceeding ±25% of the cross section of the suture needle. The mesh preferably has holes with an average diameter in the range of 5 μm to 5 mm, more preferably 50 μm to 1 mm. The width of the mesh is preferably 1 mm to 20 mm, more preferably 1 mm to 10 mm, and even more preferably 1 mm to 7.8 mm. The width may vary along the length of the mesh. In one embodiment, the mesh may have a similar elasticity to the tissue at the site of implantation. For example, in the case of abdominal tissue repair, the mesh suture preferably has the same elasticity as, or a similar elasticity to, the abdominal tissue. In another embodiment, the elasticity of the mesh is designed to allow greater tension to be applied to the reapposed tissues to keep them in close proximity to each other. Preferably, the elongation of the mesh suture is less than 30%, more preferably less than 20%. It is also desirable for the mesh to be flexible enough to pass through tissue with small curvatures.In a preferred embodiment, the mesh suture has a stiffness of less than 5 Taber Units (TU), more preferably less than 1 TU, and even more preferably less than 0.8 TU. In yet another embodiment, the mesh suture has a strength retention under physiological conditions in vivo of at least 75% at 4 weeks, more preferably at least 80% at 4 weeks, and even more preferably at least 65% at 12 weeks.
[0121] Sutures, braids, suture tapes, mesh sutures, meshes, patches, and annular knits made from high tensile strength yarns and monofilament fibers of poly(butylene succinate) and its copolymers are used in a variety of procedures including ligament and tendon repair, hernia repair, pelvic floor reconstruction, pelvic organ prolapse repair, Bankart lesion repair, SLAP lesion repair, acromio-clavicular repair, capsular shift / capsular labrum reconstruction, deltoid repair, shoulder labrum repair, hip capsule / labrum repair, rotator cuff tear repair, biceps tenodesis, mid / lateral foot and ankle repair and reconstruction, midfoot and forefoot repair, hallux valgus reconstruction, metatarsal ligament / tendon repair and reconstruction, Achilles tendon repair, ulnar or radial collateral ligament reconstruction, lateral epicondylitis repair, biceps tendon reattachment, knee extracapsular repair, iliotibial band tenodesis, patellar tendon repair, VMO advancement, knee capsule closure, hand and wrist collateral ligament repair, navicular lunate ligament reconstruction, phalangeal and tendon transfer, volar plate reconstruction, acetabular labrum repair, anterior ligament repair, spinal repair, fracture fixation, cardiovascular surgery, general surgery, stomach surgery, intestinal surgery, abdominoplasty, lift, forehead lift, brow lift, eyelid lift, face lift, neck lift, breast lift, plastic, cosmetic and reconstructive surgery, collateral canthectomy, nipple lift, breast reconstruction, breast reduction, breast augmentation, mastopexy, cystocele and rectal prolapse repair, low anterior resection, urethral suspension, obstetric and gynecologic surgery, Nissen fundoplication, myomectomy, hysterectomy, sacral resection, cesarean section, unilateral It can be used in general soft tissue access and ligation, wound closure including deep wound closure and reduction of wide scars and wound hernias, hemostasis, anastomosis, abdominal closure, reinforcement of suture repairs, laparoscopic surgery, partial nephrectomy, vascular grafts, and implantation of cardiac rhythm management (CRM) devices including pacemakers, defibrillators, generators, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medications and fluids, intrathecal delivery systems, pain pumps, and other devices for providing drugs or electrical stimulation to parts of the body. B. Mesh products
[0122] The discovery that fibers of PBS and its copolymers can be prepared with high initial tensile strength and long-term strength retention has made it possible to develop mesh implants, particularly for use in surgical procedures requiring long-term strength retention. Remarkably, fibers can be prepared with properties suitable for forming surgical meshes.
[0123] As discussed above, it has been discovered that it is possible to prepare fibers of PBS and its copolymers that do not degrade in the first 4 weeks, and preferably in the first 12 weeks, due to surface erosion that can cause indentations in the surface of the fiber. Indentation of the fiber is detrimental to the burst strength of the mesh formed from the fiber, especially when the fiber diameter is small. The absence of indentation allows for the production of meshes of PBS and its copolymers with more predictable degradation rates.
[0124] It has also been discovered that meshes with improved dimensional stability after implantation can be formed from PBS and its copolymers. As shown in Example 15 and Table 8, meshes containing PBS and its copolymers remain dimensionally stable for at least 4 weeks, more preferably at least 12 weeks, after implantation. This is a surprising result in light of the comparative data obtained for meshes made from various materials shown in Table 9. This finding is particularly meaningful when the mesh is used in procedures where it is undesirable for the mesh to shrink and place additional tension on the mesh. Thus, meshes derived from PBS and its copolymers, preferably meshes containing monofilament or multifilament oriented fibers, preferably knitted or woven meshes, are particularly suitable for use in procedures such as hernia repair, breast reconstruction, mastopexy, tissue elevation, treatment of stress urinary incontinence, repair of pelvic organ prolapse, and reconstruction of the pelvic floor. Porous meshes containing PBS and its copolymers are particularly suitable for applications where it is desirable to obtain tissue ingrowth, such as hernia repair, breast reconstruction, treatment of stress urinary incontinence using slings, and reconstruction or repair of the pelvic floor.
[0125] Meshes made from PBS and its copolymers were also found not to curl after implantation in vivo, another improvement as it prevents curled edges from potentially damaging nearby tissue.
[0126] In one embodiment, the mesh products can be manufactured from high tensile strength yarns and high tensile strength monofilaments of poly(butylene succinate) and its copolymers, for example by warp knitting or weft knitting processes. In a particularly preferred embodiment, high strength monofilaments of poly(butylene succinate) and its copolymers are used. Mesh products can be made by knitting or weaving monofilament fibers. In one embodiment, monofilament knitted mesh can be prepared using the following procedure: 49 spools of high-strength poly(butylene succinate) or copolymer monofilaments are attached to a creel, aligned side-by-side, and pulled under uniform tension toward the upper surface of a "kissing" roller. The "kissing" roller rotates while half-immersed in a bath filled with a 10% solution of polyethylene glycol sorbitan monolaurate, polyethylene glycol, or other suitable lubricant. The lubricant is deposited on the surface of the sheet of fibers. After application of the lubricant, the sheet of fibers is fed to a comb guide and wound onto a warp beam. A warp is a large, wide cylinder onto which individual fibers are wound in parallel to create a sheet of fibers. The warp beam is then processed into a finished mesh fabric using intermeshing knit loops. Eight warp beams are attached in parallel to the delivery section of a tricot machine and fed to the knitting elements at a constant speed determined by the "runner length". Each individual monofilament fiber from each beam is fed through a series of dynamic tension elements to a knitting "guide." Each fiber is passed through a single guide fixed to a guide bar. The guide bar directs the fibers around the needles to form the mesh fabric structure. The mesh fabric is then pulled away from the needles by a take-up roller at a constant speed determined by the "quality" of the fabric. The mesh fabric is then removed and wound onto a roll ready for washing. The monofilament mesh of poly(butylene succinate) or its copolymers may then be ultrasonically cleaned in water, (i) heat set (e.g., in a heated conductive liquid bath or oven), and then (ii) washed with 70% aqueous ethanol.
[0127] In one embodiment, a mesh made from monofilaments, multifilaments, or combinations thereof of poly(butylene succinate) or its copolymers has the following properties: (i) a suture pull-out strength of at least 10 N, or at least 20 N; (ii) a burst strength of 0.1-100 kgf, more preferably 1-50 kgf, or greater than 0.1 kPa; (iii) a thickness of 0.05-5 mm; and (iv) a thickness of 5-800 g / m. 2 (v) an areal density of 5 μm to 5 mm, more preferably 100 μm to 1 mm, (vi) a Taber stiffness of at least 0.01 Taber stiffness units, more preferably 0.1 to 19 Taber stiffness units, (vii) a degradation rate such that the weight average molecular weight of the mesh decreases by 10% to 30% over a 12 week period at 37° C. in phosphate buffered saline, and (viii) a degradation rate such that the burst strength of the mesh decreases by less than 20% in 4 weeks or the burst strength of the mesh decreases by less than 35% in 12 weeks under physiological conditions in vivo. In a preferred embodiment, the monofilament or multifilament mesh has one or more of the following properties: (i) a suture pull-out strength of 1 kgf to 20 kgf, (ii) a burst strength of 1 to 50 kgf, more preferably 5 to 30 kgf, (iii) a thickness of 0.1 to 1 mm, (iv) a Taber stiffness of 100 to 300 g / m 2 and (v) a pore size between 100 μm and 1 mm. In another preferred embodiment, the monofilament or multifilament mesh of poly(butylene succinate) or its copolymers has one or more of the following characteristics: a pore size of 500±100 μm, a thickness of 0.4±0.3 mm, a mass of approximately 182±50 g / m 2 a suture pull-out strength of 5.6±2 kgf, and a burst strength of at least 3 kgf, more preferably at least 6 kgf.
[0128] In one embodiment, the mesh can be combined with an anti-adhesion coating or film on one surface to create an implant. For example, the mesh can be coated on one side with a hydrogel barrier such as Sepra® coating, or with a separate hyaluronic acid coating. A particularly preferred mesh comprises oriented monofilament fibers of PBS or its copolymers coated with an anti-adhesion coating or film on one side of the mesh. Meshes coated with anti-adhesion coatings or films are particularly useful in hernia repair to prevent adhesion to internal organs.
[0129] In another embodiment, the mesh of poly(butylene succinate) or its copolymers may include fibers of different sizes including multifilaments or other non-poly(butylene succinate) or its copolymer fibers, and fibers and hybrid meshes made from other absorbable or non-absorbable biocompatible polymers. Such meshes may be designed such that the fibers degrade at different rates in vivo.
[0130] Meshes comprising poly(butylene succinate) and copolymers thereof prepared as described herein may have two-dimensional shapes including polygonal shapes, including rectangular, square, triangular, and diamond shapes, curvilinear shapes, including circular, semicircular, elliptical, and crescent shapes.
[0131] In yet another embodiment, the meshes described herein can be used to prepare three-dimensional implants, such as implants that can be used for breast reconstruction, mastopexy, hernia repair, or cavity filling. Three-dimensional shapes include cone, dome, partial dome, canoe, hemisphere, plug, and semi-ellipse shapes. In one embodiment, these three-dimensional implants have a shape memory that can be used to conform to an anatomical shape or to be given the shape of the patient's tissue. For example, these three-dimensional implants can be used in mastopexy and breast reconstruction to be given the shape of the host breast tissue or to form the anatomical shape of the breast. In one embodiment, these three-dimensional implants have a shape memory that can resume their three-dimensional shape after being delivered into the body (e.g., laparoscopically delivered), for example, through a trocar or similar delivery device. These three-dimensional implants can be used for laparoscopic inguinal hernia repair, where the implant has a three-dimensional shape suitable for conforming to the anatomical shape of the groin and retains its shape after laparoscopic introduction. A suitable three-dimensional implant of poly(butylene succinate) and its copolymers can be manufactured by molding a two-dimensional monofilament mesh made from poly(butylene succinate) and its copolymers. In one process, the mesh can be molded using a metal split mold consisting of an inwardly curved half and a mating outwardly curved half. The three-dimensional implant is formed by placing the mesh over the inwardly curved half of the metal mold, placing the outwardly curved half of the metal mold on top of the mesh, clamping the metal split molds together to form a block, and heating the block to mold the mesh. In another process, the three-dimensional implant can be a plug, preferably a hernia plug, made from a mesh of poly(butylene succinate) and its copolymers.
[0132] In another embodiment, a three-dimensional implant of poly(butylene succinate) and its copolymers may be implanted in the breast, preferably in place of a breast implant. In a particularly preferred embodiment, the three-dimensional implant comprises pleats, chambers, or compartments. Preferably, the pleats, chambers, and compartments are made with monofilament fibers of poly(butylene succinate) and its copolymers. The chambers or compartments are filled with tissue during implantation, for example, the chambers or compartments may be filled with one or more of the following: cells, including stem cells, proteins, including collagen, fat, and fascia. In a particularly preferred embodiment, the three-dimensional implant may have a lotus or funnel-shaped shape. In an even more preferred embodiment, the three-dimensional implant may have a lotus or funnel-shaped shape and is made from monofilament fibers of poly(butylene succinate) or its copolymers.
[0133] Preparing an expandable mesh comprising poly(butylene succinate) or its copolymers These meshes can be prepared such that the fibers of the mesh can stretch or elongate, thereby allowing the mesh to expand. The meshes may include unoriented, partially oriented, or fully oriented fibers of poly(butylene succinate) or its copolymers. The meshes may be designed such that the fibers of the mesh can expand without stretching. In one embodiment, the meshes may have a knit pattern that gives the mesh the ability to stretch under force. For example, the meshes may include pores that can stretch under force, or loops that can shorten when force is applied. In another embodiment, the meshes may include a combination of strong and weak fibers, where the weak fibers break when force is applied, allowing the mesh to stretch. Expandable meshes including poly(butylene succinate) or its copolymers are particularly suitable for use in breast reconstruction, more specifically in combination with the use of tissue expanders. The expandable meshes preferably include monofilament fibers made from poly(butylene succinate) and its copolymers.
[0134] In further embodiments, the meshes described herein may further include barbs, hooks, self-anchoring tips, microgrips, fleeces, reinforcing materials, and reinforced outer edges or borders.
[0135] In another embodiment, nonwoven meshes can be prepared from high tensile strength yarns by entangling the fibers using mechanical methods. The properties of the nonwoven fabric can be tailored by selection of parameters such as fiber diameter, fiber orientation, and fiber length (for staple nonwoven fabrics). In a preferred embodiment, nonwoven meshes prepared from high tensile strength yarns have the following properties: (i) a thickness of 0.1-5 mm; (ii) a fiber length of 5-800 g / m 2 (iii) a suture pull-out strength of greater than 10 N; and (iv) a burst strength capable of withstanding a pressure of at least 0.1 kPa.
[0136] In another embodiment of the invention, high tensile strength yarns of poly(butylene succinate) and its copolymers can be knitted to produce a circular knit. The circular knit containing high tensile strength yarns can be used, for example, as a vascular graft. In one embodiment, the circular knit of high tensile strength yarns of poly(butylene succinate) and its copolymers can be produced using a single feed circular weft knitting machine (Lamb Knitting Co., model ST3A / ZA).
[0137] In another preferred embodiment of the present invention, it has been discovered that implantable meshes can also be formed by 3D printing. These meshes are particularly suitable for use in breast reconstruction, hernia repair, pelvic floor reconstruction, and treatment of stress urinary incontinence using slings. Two different methods of 3D printing poly(butylene succinate) and its copolymers are described in Examples 9 and 10. Figure 1 shows an image of a mesh 3D printed according to the method of Example 9. The high quality of the mesh is evident from the image. This method is particularly suitable for forming three-dimensional mesh implants including PBS and its copolymers, including, for example, hernia plugs, and meshes with three-dimensional shapes designed to follow the patient's anatomy. This method can be used to form PBS and its copolymers for breast reconstruction, including breast implants, expandable meshes, and full contour implants. It can also be used to prepare 3D meshes of copolymers. In one embodiment, the 3D printed mesh implant comprising PBS or its copolymers has one or more of the following properties: a burst strength of 1 kgf to 25 kgf, more preferably 3 kgf to 10 kgf, a thickness of 50 μm to 3 mm, more preferably 100 μm to 800 μm, a pore size of 75 μm to 5 mm, a total porosity of at least 50% but less than 100%, and a weight average molecular weight by GPC of 25 kDa to 500 kDa, more preferably 50 kDa to 300 kDa for polystyrene.
[0138] Meshes comprising PBS and copolymers thereof disclosed herein can be used as implants for wound closure devices, patches, wound healing devices, devices for tissue or suture reinforcement, tracheal reconstruction devices, organ retrieval devices, dura patches or replacements, devices for nerve regeneration or repair, hernia repair devices, hernia meshes, hernia plugs, inguinal hernia plugs, devices for temporary wound or tissue support, tissue engineering scaffolds, guided tissue repair / regeneration devices, anti-adhesion membranes or barriers, tissue isolation membranes, retention membranes, slings, Pelvic floor reconstruction devices, urethral suspension devices, devices for the treatment of urinary incontinence, bladder repair devices, void filling devices, bone marrow scaffolds, ligament repair or strengthening devices, anterior cruciate ligament repair devices, tendon repair or strengthening devices, rotator cuff repair devices, meniscus repair or regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, cardiovascular patches, vascular closure devices, intracardiac septal defect repair devices, atrial septal defect repair devices, patent foramen ovale closure devices, left atrial appendage closure devices, pericardial patches, vascular grafts , myocardial regeneration devices, periodontal meshes, guided tissue regeneration membranes for periodontal tissue, imaging devices, anastomosis devices, devices for cell seeding, devices for controlled release, devices for drug delivery, plastic surgery devices, devices for breast lift, devices for mastopexy, devices for breast reconstruction, devices for breast enlargement, devices for breast reduction, devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift, devices for eyelid lift, devices for face lift, devices for rhytidectomy, devices for rhinoplasty, Cheekbone augmentation devices, otoplasty devices, neck lift devices, chinplasty devices, buttock lift devices, cosmetic repair devices, devices for facial scar correction, pouches, holders, covers, housings or casings for partially or completely enclosing, surrounding or holding implantable medical devices, cardiac rhythm management devices, pacemakers, defibrillators, generators, implantable access systems, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medicines and fluids, intrathecal delivery systems, pain pumps,Or they can be used in devices that provide drugs or electrical stimulation to the body. C. Orthopedic Implants
[0139] In one embodiment, orthopedic implants can be prepared from the polymer composition comprising poly(butylene succinate) and its copolymers. Optionally, these implants can comprise ceramic or bioceramic. In one embodiment, implants, including screws, pins, ACL screws, clips, clamps, nails, medullary canal nails, bone plates, tacks, fasteners, rivets, staples, fixation devices, bone void fillers, suture anchors, bone anchors, osteochondral repair devices, spinal fixation devices, and devices for treating osteoarthritis, optionally with ceramic, are formed from poly(butylene succinate) and its copolymers. It has been discovered that compositions of poly(butylene succinate) and its copolymers can be made into implants with high stiffness and torsional strength, making them suitable for use in orthopedic implants.
[0140] In one embodiment, the orthopedic implants can be manufactured by injection molding. For example, injection molded implants of PBS and its copolymers can be formed using an Arburg Model 221 injection molding machine with the following conditions: machine barrel temperature ramps from 70°C in the feed zone to 170°C at the end of the barrel, and a mold temperature of 32°C. After molding, the implants are dried in a vacuum oven at room temperature for 48 hours and tensile properties are determined using an MTS testing machine with a crosshead speed of 2 inches / minute. Representative tensile properties of implants formed by this method are as follows: Young's modulus 0.66 GPa (96,600 psi), yield strength 49.2 MPa (7,140 psi), and break stress 71.7 MPa (10,400 psi). Example 8 discloses the manufacture of interference screws by injection molding. Screws made from PBS and its copolymers. The torsional strength of the interference screw is preferably 10-18 Ncm. This strength can be further increased by blending the polymer composition with a ceramic prior to injection molding. A preferred ceramic is tricalcium phosphate. A preferred blend ratio is 10-50 wt% ceramic. As disclosed in Example 8, interference screws prepared with bioceramics can have a torsional strength of at least 10-20 Ncm. D. Other implants
[0141] In one embodiment, absorbable stents can be prepared from poly(butylene succinate) or copolymers thereof by first fabricating a tubular stent blank. The tube can be prepared by melt extrusion, injection molding, solvent dipping, or similar processes that provide a consistent tube thickness of approximately 0.001-0.500 mm. The stent structure can be cut into blanks using mechanical or laser processes that remove material from selected areas of the tube blank. The stent can be delivered to a location in the body and deployed by balloon expansion, or if the stent is self-expanding, can be removed from a sheath in the body and allowed to self-deploy. The stent structure provides support to nearby tissue and / or delivers a therapeutic agent that may be included in the stent material or coated on its surface.
[0142] In another embodiment, microbeads can be prepared from poly(butylene succinate) or its copolymers using solvent or melt processing approaches. The microbeads can contain a therapeutic agent and deliver the agent to the tissue after being injected into the tissue. The beads can also be used to occlude blood vessels or provide additional volume to tissue.
[0143] In further embodiments, the staple line reinforcement material can be prepared from poly(butylene succinate) or its copolymers using methods for preparing medical fabrics, such as knitting, weaving, or nonwoven processes. Alternatively, the staple line reinforcement material can be manufactured from a porous foam of poly(butylene succinate) or its copolymers. The staple line reinforcement material can be used to provide a backing for weakened or brittle tissues that cannot be reliably supported by surgical staples or sutures. In this manner, the staple line reinforcement material can also function as a pledget or backing material for surgical sutures. Additionally, the staple line reinforcement material can also be used to seal tissues and prevent leakage of air, blood, or other bodily fluids during surgical repair. This can aid in procedures that allow surgeons to more quickly, consistently, and reliably perform surgical incisions, staple line reinforcement repairs, or anastomoses on tissues such as lungs, blood vessels, intestines, or similar tissues.
[0144] In another embodiment, poly(butylene succinate) or its copolymers can be prepared into absorbable clips for tissue ligation using melt processing techniques such as injection molding or 3D printing.Absorbable clips can be used when permanent clips are not desired or to treat temporary conditions.Absorbable clips or cuffs can be useful to prevent or stop bleeding and restrict the flow of materials or fluids through blood vessels.Bariatric clips or cuffs are preferred for the treatment of obesity or eating disorders, and are preferred over permanent, invasive surgery.
[0145] In yet another embodiment, absorbable filters for capturing thrombi can be prepared from poly(butylene succinate) or its copolymers. Such vena cava filters may be preferred over permanent metal or polymeric filters because they avoid the need for a second surgery to remove the filter after it is no longer needed. V. METHODS OF DELIVERING IMPLANTS MADE FROM POLY(BUTYLENE SUCCINATE) AND ITS COPOLYMERS
[0146] Implants made from poly(butylene succinate) and its copolymers can be implanted using conventional open surgical techniques, but can also be implanted using minimally invasive techniques. In one embodiment, high strength sutures are implanted using arthroscopic techniques. In a particularly preferred embodiment, high strength sutures and suture tapes are used for arthroscopic repair of the shoulder, elbow, wrist, spine, hip, knee, ankle, and foot, including ligament and tendon repair. In another embodiment, meshes, webs, and lattices made from high strength monofilaments or high tensile strength yarns of poly(butylene succinate) and its copolymers, or by 3D printing, can be implanted using laparoscopic techniques. In a preferred embodiment, meshes, webs, and lattices are implanted for hernia repair and lift using laparoscopic and other minimally invasive techniques.
[0147] In a particularly preferred embodiment, the implants may be used in any current mastopexy technique to achieve breast lift using any suitable skin excision pattern. The method selected will depend on the degree of breast ptosis and several other factors. The four main techniques of mastopexy are crescent mastopexy, donut (or Benelli) mastopexy, lollipop (or vertical) mastopexy, and anchor (or Weiss or Wise) mastopexy. In crescent mastopexy, a semicircular incision is made above the areola and a crescent-shaped piece of breast tissue is removed. This technique is typically used in patients with only mild ptosis where good lift can be achieved by removing excess skin on the top of the breast and suturing the skin back to elevate the areola-nipple complex. In one embodiment, the implants can be placed after further dissection and / or resection to provide additional support to the tissue on the top of the breast.
[0148] Implants can also be placed during a doughnut or Benelli mastopexy, in which a doughnut-shaped piece of breast skin is removed from around the areola with a medial incision following the areola and a lateral incision going further around the areola. In one embodiment, after further dissection to support lift, the implant is inserted and a purse string suture can be used to bring the breast skin back closer to the areola.
[0149] In both lollipop and anchor mastopexy, an incision is made around the areola complex. In the lollipop procedure, a vertical incision is made in the lower breast from the areola to the inframammary fold. In anchor mastopexy, an incision is made across the inframammary fold in addition to the vertical incision used in the lollipop procedure. The lollipop procedure is generally used for patients with moderate ptosis, while the anchor procedure is usually reserved for patients with more severe ptosis. These two procedures can be performed with or without breast implant augmentation. In both procedures, breast tissue is excised and the excised edges are sutured together to create an elevation. Before suturing the excised tissue, an implant can be placed to support the breast and reduce the forces on the excised skin and sutures after closure. In a particularly preferred embodiment, the implant is positioned to support the breast parenchyma or implant and minimize the weight of the breast on the skin and sutures. In an even more preferred technique, the sutures are closed with minimal or no tension on the wound to minimize scarring.
[0150] In preferred embodiments, when sutured into place, the implant supports, lifts, and shapes the breast by anchoring the implant to one or more of the tissue, muscle, fascia, or bone of the chest or torso. In particularly preferred embodiments, the implant is sutured to the pectoral fascia or clavicle. The implant may be sutured to the chest wall or fascia, and in particularly preferred embodiments, the implant supports the lifted breast or breast implant. The catheter may be sutured to the chest wall to provide a sling for support.
[0151] Modifications and variations of the invention described herein will be obvious to those of skill in the art and are intended to be included within the scope of the appended claims.
[0152] The invention will be further understood by reference to the following non-limiting examples. EXAMPLES
[0153] Example 1 Monofilament melt extrusion of succinic acid-1,4-butanediol-malic acid copolyester with two-stage orientation in a convection chamber to produce monofilament fibers for implant applications Succinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) with a weight average molecular weight of 184 kDa and a Tm of 115°C (melt flow rate (MFR) at 190°C / 2.16 kgf: 5 g / 10 min) was dried under vacuum overnight to a moisture content of less than 0.01% (w / w). The dried polymer pellets were fed under nitrogen into the extrusion barrel of an AJA (Alex James Associates, Greer, SC) 3 / 4 inch single screw extruder (L:D=24:1, compression ratio 3:1) equipped with a Zenith-type metering pump (0.16 cc / rev) and a die with a single hole spinneret (0.026 inch, L:D=2:1). The four heating zones of the extruder were set at 75°C, 165°C, 180°C, and 180°C. A quench bath filled with 35°C water was attached to the extruder and the air gap between the bottom of the spinneret and the surface of the water was set at 10 mm. Two two-roll godets were positioned after the quench bath, followed by two sets of longitudinal heated convection chamber / two-roll godet combinations. The temperature of the heated convection chamber was set at 60°C-80°C, followed by the two-roll godet, followed by the horizontal winder. The copolyester pellets entered the heated extruder barrel and the molten polymer passed through the barrel, entering a heated block, then a metering pump, followed by a single-hole spinneret. The block, metering pump, and spinneret die were maintained at a constant temperature, preferably 180°C. The pump discharge pressure was kept below 1500 psi by controlling the temperature and metering pump speed. The resulting spun extruded filaments were free of any melt misalignment. The extrudate was quenched in a water bath, pulled through a longitudinal oven, and wound on a horizontal tension-controlled Sahm winder. The results of three tests oriented in-line are shown in Table 1, along with the results of a fourth test in which the fibers were not oriented in-line but were oriented off-line 10 days after extrusion. An examination of Table 1 reveals that the conditions used to prepare the monofilament fibers resulted in fibers having tensile strengths ranging from 434 to 518 MPa. [Table 1]
[0154] Example 2 Monofilament melt extrusion of succinic acid-1,4-butanediol-malic acid copolyester with multi-stage incremental orientation in a conductive chamber to produce monofilament fibers for implants
[0155] Weight average molecular weight 184kDa, P D Succinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) (MFR: 5 g / 10 min at 190 °C, 2.16 kgf) with pH = 2.83 and Tm = 115 °C was dried overnight under vacuum to a moisture content of less than 0.01% (w / w). The dried polymer pellets were fed under nitrogen into the extrusion barrel of an American Kuhne 2.5 inch single screw extruder (L:D = 30:1, compression ratio 3:1) equipped with a Zenith type metering pump (model HPB917), a die with a 0.5 mm 8-hole spinneret, and eight heating zones. The eight heating zones of the extruder were set at 40 °C to 200 °C. A quench bath filled with water at 35 to 70 °C was attached to the extruder and the air gap between the bottom of the spinneret and the surface of the water was set at 10 mm. Two five-roll godets were positioned after the quench bath, and three sets of heated conductive chambers fed by the godets were installed to orient the fibers in multiple stages. The temperature of the heated chambers was set at temperatures between 50°C and 90°C. Another godet was positioned after the last chamber, followed by a multi-position Sahm winder. The results of three trials are shown in Table 2. Compared to the results shown in Table 1, the multiple incremental orientation of the fibers and the use of a conductive chamber instead of the standard conventional non-liquid chamber resulted in monofilament fibers with substantially higher tensile strengths of 779-883 MPa. [Table 2]
[0156] Example 3 Multifilament extrusion of succinic acid-1,4-butanediol-malic acid copolyester to prepare implants
[0157] Weight average molecular weight 184kDa, P DSuccinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) (Melt flow rate (MFR) at 190°C / 2.16 kgf: 5 g / 10 min) with pH = 2.83 and Tm = 115°C was dried under vacuum overnight to a moisture content of less than 0.01% (w / w). The dried polymer pellets were fed into the extrusion barrel of an AJA (Alex James Associates, Greer, SC) 3 / 4 inch single screw extruder (L:D = 24:1). The extrusion barrel contained four heating zones, a metering pump, and a spin pack assembly. The pellets were gravity fed into a cooled feeder section and introduced into the extruder with the following temperature profile set as follows: Chimney: 40°C-100°C, Spinneret: 170°C±30°C, Pump: 170°C±30°C, Block: 170°C±30°C, Zone 4: 160°C±40°C, Zone 3: 150°C±40°C, Zone 2: 120°C±50°C, Zone 1: 30-40°C, Feed Zone: Ambient Temperature. The heated and homogenized molten resin from the extruder was fed into a heated metering pump (melt pump), and the extruded resin was fed from the melt pump into the heated block and spinneret assembly. The spinneret had a capillary diameter of 0.200 mm and 30 holes with a L / D ratio of 2:1 (the spinneret may be configured in other alternative styles, e.g., the spinneret may be configured with capillary diameters of 0.150-0.300 mm (6 mils-12 mils), 15, 120, and 240 holes, as well as larger and smaller diameters and numbers of holes). The processing temperature profile ranged from 35°C to 250°C, with pressures ranging from 200 to 5,000 psi in the barrel and 200 to 5,000 psi in the spin pack. As the molten filaments exited the spin pack, they passed through a heated chimney collar 6-12 inches long and with a temperature range of 40°C to 100°C, and then through an air quench box. The spin pack was suspended vertically above the yarn take-up roll at a distance sufficient to allow crystallization of the molten filaments and application of a spin finish lubricant. A spin finish aqueous solution of 25% polyethylene 25 glycol 400 (PEG400) was used to hold the filaments together to form the yarn bundle.The speed of the yarn take-up rolls to control the denier of the spun yarn bundle. The spin finish was reactivated by rewetting the yarn bundle with pure water and the yarn was drawn at ratios of 5 to 14 times, at temperatures ranging from 50°C to 90°C. The tensile strength and denier of the produced multifilament yarns are shown in Table 3. [Table 3]
[0158] Example 4 2. Preparation of Multifilament Sutures
[0159] Oriented yarns produced according to Example 3 and having the properties shown in Table 3 were braided using 8 and 16 carrier Steeger braiding equipment to form the braided constructions shown in Table 4. The mechanical properties of the high strength braided sutures, determined according to USP 24, are also shown in Table 4. Examples include a braid formed as a tape (shown as the last example in Table 4).
[0160] [Table 4] Example 5 2. Preparation of Knitted Monofilament Mesh Implants
[0161] Monofilament fibers (USP suture size 5 / 0) prepared according to the method of Example 2 were processed into a knitted mesh according to the following procedure. Forty-nine spools of monofilament fibers were attached to a creel, aligned side-by-side, and pulled under uniform tension toward the upper surface of a 10-inch "kissing" roller. The "kissing" roller was rotated while half-immersed in a bath filled with a 10% solution of TWEEN® 20 lubricant. TWEEN® 20 lubricant was added to the creel and the mesh was then spun into a mesh mesh. A TWEEN® 20 lubricant was deposited on the surface of the sheet of monofilament fibers. After application of the TWEEN® 20, the sheet of fibers was fed to a comb guide and then wound onto a warp beam. The warp is a large, wide cylinder onto which individual fibers are wound in parallel to create a sheet of fibers. The warp beam was then converted into a finished mesh fabric using intermeshing knit loops. Eight warp beams were attached in parallel to the pay-off of the tricot machine and fed to the knitting elements at a constant speed determined by the "runner length". Each individual monofilament fiber from each beam was fed to a knitting "guide" through a series of 20 dynamic tension elements. Each fiber was passed through a single guide fixed to a guide bar. The guide bar directed the fibers around the needles to form the structure of the mesh fabric. The mesh fabric was then pulled away from the needles by a take-off roller at a constant speed determined by the "quality" of the fabric. The mesh fabric was then removed, wound onto a roll, ultrasonically washed in water, heat set in hot water, and then washed with 70% aqueous ethanol. The knitted mesh made with the monofilament fiber of Example 2 had the following properties (as shown at Time 0 in Table 11): burst strength of 22.668 kgf, caliper of 0.683 mm, and Taber stiffness of 0.116. Example 6 2. Preparation of Knitted Multifilament Mesh Implants
[0162] Spools of multifilament fiber prepared according to the method of Example 3 were processed into a knitted multifilament mesh using the method described in Example 5. Example 7 Injection Molded Implants
[0163] Injection molded implants made of succinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) with a weight average molecular weight of 184 kDa and a Tm=115°C were prepared using an Arburg Model 221 injection molding machine using the following conditions: The barrel temperature of the machine was increased from 70°C in the feed zone to 170°C at the end of the barrel. The mold temperature was maintained at 32°C. After molding, the implants were dried in a vacuum oven at room temperature for 48 hours and tensile properties were determined using an MTS testing machine at a crosshead speed of 2 inches per minute. Representative tensile properties of the implants were as follows: Young's modulus 0.66 GPa (96,600 psi), yield strength 49.2 MPa (7,140 psi), and break stress 71.7 MPa (10,400 psi). Example 8 Injection molded interference screw for use as an implant
[0164] Interference screws 7 mm in diameter and 20 mm in length were injection molded from succinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) and from the same copolyester blended with 50 wt% beta-TCP (tricalcium phosphate). The screws were formed using a procedure similar to that described in Example 7. After the screws were injection molded, the intrinsic viscosity of the composition was essentially equivalent to that of the starting material, indicating that little loss of weight average molecular weight occurred during injection molding. The torsional strength of the screws was determined by embedding the tips of the molded screws in epoxy resin and measuring the maximum torque achieved by the screw driver before the screw broke. A torsional strength value of 15.0 Ncm was obtained as the average of three screws tested with the copolyester alone. The test was repeated with screws prepared from the blend, with an average value of 18.2 Ncm. For comparison, a commercially available Arthrex Biointerference screw for implantation made of PLLA (poly-L-lactic acid) was also tested. The Arthrex Biointerference screw has a mean failure torque of 12.1 Ncm. Example 9 3D printed embeddable mesh
[0165] A 3D printed mesh was prepared from succinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) with a weight average molecular weight of 184 kDa and Tm=115 °C using melt extrusion deposition by the following method. The mesh was printed using an ARBURG Free-Former machine consisting of a horizontal extruder feeding a vertical ram extruder fitted with a motion-controlled needle plunger, a 200 micron spinneret nozzle, and a movable stage table. The extruder hopper was charged with polymer pellets measuring 1.5 mm x 3 mm with a moisture content of less than 2,000 ppm. The pellets were purged with dry nitrogen in the extruder hopper to maintain dry conditions. The extruder temperature profile was set from 45 to 180 °C, and the residence time of the polymer in the extrusion system was maintained at less than 15 min / cm. This condition resulted in the formation of a very high quality printed mesh as shown in Figure 1. Example 10 3D printed embeddable lattices
[0166] 3D printed lattices were prepared using selective laser melting (SLM) from succinic acid-1,4-butanediol-malic acid copolyester (Tepha lot 180333) with a weight-average molecular weight of 184 kDa and Tm = 115 °C. The SLM apparatus consisted of a movable powder bed equipped with a container for the polymer granules and a powder sweeper gate valve, as well as a laser source capable of directing a laser beam into the powder bed and focusing it on a single polymer granule in the bed. The positions of both the movable powder bed and the laser beam were controlled by a computer programmed with 3D CAD data for producing lattice structures of the copolyester. The powder bed was movable in the XY horizontal plane and also in the Z-axis vertical plane. The focal length, i.e. the distance between the lens and the surface of the powder, was less than 50 cm. Prior to printing, the polymer was freeze-milled using liquid nitrogen and sieved to produce granules with an average size of 0.3-250 μm. The granules were placed in a powder container and a powder sweeper was used to spread a first layer of powder 250 μm thick onto a moving bed. A computer-driven laser beam was focused on each polymer granule, moving from one granule to the next as it melted, until the granules were melted. After printing the first layer, the sweeper arm spread a second layer of polymer granules, the laser was positioned to focus on the granules, and the laser irradiation was initiated to form the second 3D layer. The process was repeated with successive layers until a lattice made from succinic acid-1,4-butanediol-malic acid copolyester was formed. Example 11 Endotoxin test of copolymers of succinic acid and 1,4-butanediol
[0167] The endotoxin content of the polymer pellets made of succinic acid-1,4-butanediol-malic acid copolyester was measured using USP <85> The Bacterial Endotoxin Test (BET) Gel Clot method was used. Prior to testing, the pellets were sterilized by exposure to ethylene oxide gas. Extractions were performed at a ratio of 1 g of polymer in 10 mL of endotoxin-free water, and 8-fold dilutions of the sample extract were prepared and tested by the gel clot method. Results were less than 2.5 EU / g polymer. Example 12 In vitro degradation of implantable meshes prepared from succinic acid-1,4-butanediol-malic acid copolyesters
[0168] The in vitro degradation rate of implantable meshes prepared from oriented monofilament fibers composed of succinic acid-1,4-butanediol-malic acid copolyester (prepared as described in Example 5) was determined by incubating the meshes in phosphate buffered saline. The degradation of the buffer solution was studied by filtration. The buffer solution contained 137 mM NaCl, 2.7 mM KCl, 9.8 mM phosphate, and 0.05 wt% sodium azide and had a pH of 7.4 at 25°C. The prepared buffer solution was filtered through a 0.45 μm filter (VWR, product number 10040-470) before use. The mesh samples were sterilized by exposure to ethylene oxide gas. The samples (2 x 2 inches) were placed in a sterile container, covered with the buffer solution, and incubated in a shaker incubator at 50 rpm and a temperature of 37°C. The buffer medium was monitored monthly and replaced if the pH value exceeded the target value of 7.4 ± 0.2. At the designated time points, the samples were removed from the buffer solution and washed with deionized water to remove the buffer salts. The samples were then tested for mechanical properties and retention of the polymer weight average molecular weight by gel permeation chromatography (described further in Example 15). The in vitro degradation data are shown in Table 5. [Table 5] Example 13 In vitro degradation of implantable sutures prepared from succinic acid-1,4-butanediol-malic acid copolyesters
[0169] The in vitro degradation rate of implantable sutures prepared from oriented monofilament fibers composed of succinic acid-1,4-butanediol-malic acid copolyester was studied by incubating the sutures in phosphate buffered saline. The initial properties of the sutures are shown in the first row (t=0) of Table 6. The buffer contained 137 mM NaCl, 2.7 mM KCl, 9.8 mM phosphate, and 0.05 wt% sodium azide and had a pH of 7.4 at 25°C. The prepared buffer was filtered through a 0.45 μm filter (VWR, product number 10040-470) before use. The suture samples were sterilized by exposure to ethylene oxide gas. The samples (12 inches long) were placed in a sterile container, covered with the buffer, and incubated in a shaker incubator at 50 rpm and 37°C. The buffer medium was monitored monthly and replaced if the pH value exceeded the target value of 7.4 ± 0.2. At the designated time points, samples were removed from the buffer and washed with deionized water to remove buffer salts. The samples were then tested for mechanical properties and retention of polymer weight average molecular weight (Mw) by gel permeation chromatography (described further in Example 15). The in vitro degradation data are shown in Table 6. [Table 6] Example 14 Elemental analysis of succinic acid-1,4-butanediol-malic acid copolyester
[0170] The elemental composition of succinic acid-1,4-butanediol-malic acid copolyester was analyzed using Proton Induced X-ray diffraction (PIXE) from Elemental Analysis Inc. The polymer was analyzed by Photoelectron X-ray Electron Emission (PIXE). This method provides a quantitative elemental composition of the material for inorganic elements from sodium to uranium in the periodic table. The elements found are shown in Table 7. The polymer did not contain detectable amounts of heavy metals such as tin, which may be used in the manufacture of resorbable polymers such as polyglycolide, polylactide, and polyglycolide-co-lactide. The following trace elements were detected: silicon 18.98 ppm, titanium 14.77 ppm, and zinc 5.967 ppm. [Table 7]
[0171] Example 15 Comparison of the in vivo characteristics of implantable meshes prepared from succinic acid-1,4-butanediol-malic acid copolyester with those prepared from poly-4-hydroxybutyrate
[0172] The properties of a monofilament knitted mesh prepared from a copolymer of 1,4-butanediol and succinic acid units described in Example 5 ("PBS" mesh) were compared to a commercially available mesh prepared by knitting poly-4-hydroxybutyrate monofilaments, i.e., "GalaFLEX mesh" (Galatea Surgical, Lexington, MA), in an in vivo implantation study in rabbits. The weight average molecular weight of the PBS mesh fibers prior to implantation was 173 kDa. PBS and GalaFLEX meshes were implanted into the dorsal subcutaneous tissue of New Zealand White rabbits to assess in vivo local tissue response, the extent of tissue ingrowth, and changes in the mechanical properties of the meshes over time. Six female New Zealand White (NZW) rabbits were implanted with 100% PBS mesh per animal. Six specimens (4 x 4 cm) for mechanical testing, one specimen (2 x 2 cm) for histology, and one specimen (2 x 2 cm) for scanning electron microscopy (SEM) were embedded.
[0173] Prior to implantation, rabbits (weighing at least 3.5 kg at the time of implantation) were anesthetized by intramuscular injection and subsequently maintained with isoflurane. Following anesthesia, animals were given subcutaneous injections of analgesic agents. The surgical site was prepared for implantation. An incision was made through the skin and the skin was excised laterally by blunt dissection to create a pocket. Each animal was implanted with three individual mechanical specimens (4 x 4 cm) and one histology / SEM specimen (2 x 2 cm) on each side for a total of eight specimens per animal. Specimens were implanted by laying the mesh flat along the back of the animal without folding or rolling and secured with Prolene sutures at each corner. The skin was closed and bandages applied. Animals were returned to their cages and monitored for recovery from anesthesia and subsequently monitored daily for general health.
[0174] Three rabbits from each group were euthanized at 4 and 12 weeks. The skin was everted, the subcutaneous tissue was inspected, and the area around each implant was dissected free. The implanted mesh was retrieved by dissection from the surrounding tissue. The explants were processed for histological, biomechanical, and polymer testing. Half of the 4 x 4 cm mesh implanted at each time point (n = 9) was tested for mechanical properties including ingrowth tissue. Other samples (n = 9) were designated for mesh-only analysis to assess the residual strength of the polymer scaffold remaining after collagenase digestion to remove ingrowth tissue. In this way, the mechanical properties of the mesh alone could be measured and compared to those of the mesh and tissue combination in the composite.
[0175] For mesh-only samples, explants were cleaned of ingrowth-in tissue using collagenase enzymatic digestion. Previous studies have demonstrated that collagenase enzyme does not affect the mechanical or molecular weight properties of the mesh. Each explanted mesh specimen was placed into a 50 mL Falcon tube containing 25 mL of collagenase (type I) solution (1.0 mg / mL) in TESCA buffer (50 mM TES, 2 mM calcium chloride, 10 mM NaN3, pH 7.4, sterile filtered). The tube was placed on a shaker (50 rpm) and incubated overnight (approximately 17 hours) at 37°C to digest and remove tissue attached to the mesh specimen. After incubation was complete, the specimen was removed from the tube and any remaining tissue was removed by hand from the explant, taking care not to damage the mesh, and the mesh was washed with distilled water followed by 70% ethanol. The mesh specimen was blotted dry with lint-free wipes.
[0176] Samples were tested for dimensions, relative stiffness (Taber tester), burst strength, and surface morphology was evaluated by SEM. Comparisons were made to non-implanted (T0) articles (n=9 / group). Polymer degradation was further evaluated by gel permeation chromatography (GPC). The host tissue response and extent of tissue remodeling were evaluated histologically. Burst test, stiffness, and molecular weight (Mw) retention of PBS meshes.
[0177] The thickness of each sample was measured using a Progauge thickness tester prior to the burst strength test. The burst strength was measured using a universal testing machine (MTS Qtest Elite) equipped with a 1,000N load cell, according to ASTM D6797-02, Standard Test Method for Bursting Strength of Fabrics Constant-Rate-of-Extension (CRE) Ball Burst Test. The specimen was clamped over the circular opening of the fixture and a 3 / 8 inch probe was lowered through the specimen at 305 mm / min until failure. A preload of 0.05 kg was set to remove slack in the specimen and zero displacement was registered. The load at failure (kgf) was recorded as the burst strength.
[0178] After mechanical testing, a portion of the mesh residue was taken and analyzed by gel permeation chromatography (GPC) to determine the weight average molecular weight (M w ) was measured. Mw was measured against monodisperse polystyrene standards using a TOSOH HPLC equipped with a refractive index detector. Samples for GPC were prepared at 1 mg / ml in chloroform and 100 μl of solution was injected onto a Polymer Labs PL gel column (5 μm, mixed C, 300×7.5 mm) and eluted at 1 ml / min in chloroform using a refractive index detector. The test results are summarized in Tables 8-12 below.
[0179] Tables 8 and 9 show the dimensions (mesh length, width, and area) of the PBS and GalaFLEX meshes before implantation and at 4 and 12 weeks after implantation. The data show a striking difference between the two meshes. Although both are made from similarly sized monofilament fibers in the same knit pattern, the dimensions of the PBS mesh remain essentially constant after implantation, whereas the dimensions of the GalaFLEX mesh change over time. Thus, it is apparent that the PBS mesh is dimensionally stable after implantation and does not shrink after implantation. The area occupied by the mesh remains constant as shown by the relative area occupied by the PBS mesh in Table 8, as do the dimensions of the mesh. [Table 8] [Table 9]
[0180] Table 11 shows that the burst strength of the PBS mesh decreased from 22.668 kgf to 16.801 kgf over the course of 12 weeks, representing a strength retention of 74.1%. Table 10 shows that there is less loss of burst strength due to tissue ingrowth into the PBS mesh when the explants are tested without removing the ingrowth tissue. In this case, the burst strength only decreased from 22.668 kgf to 18.288 kgf, representing a strength retention of 80.7% over the 12 week period. It is clear from this data that the PBS mesh is capable of supporting tissue ingrowth, which contributes an additional 80.7%-74.1%=6.6% to the burst strength of the mesh by 12 weeks after implantation. Table 11 also shows that the stiffness of the PBS mesh (measured in Taber stiffness units) remains relatively constant throughout the 12 week implantation period, even though the burst strength of the mesh decreases by approximately 25% at 12 weeks. [Table 10] [Table 11]
[0181] Table 12 shows the reduction in weight average molecular weight (Mw) of the PBS polymer used to prepare the PBS mesh implant at 4 and 12 weeks compared to the initial Mw. The data shows that the PBS mesh implant degrades in vivo with retention of the polymer weight average molecular weight of 89.7% at 4 weeks and 72.5% at 12 weeks. The finding of good strength retention of the PBS mesh means that it is suitable for use in procedures requiring long-term strength retention. [Table 12] Biocompatibility and histology of PBS mesh
[0182] Macroscopic examination at 4 weeks showed that the tissue had fully integrated into the pores of the mesh implant. Microscopically, all three sites showed significant ingrowth of tissue into the implant material, consisting of new fibrous connective tissue, vascularization, and inflammation extending into the spaces between the implant material fibers (i.e., the pores of the mesh).
[0183] The tissue response of the PBS mesh was graded against the commercial comparator, GalaFLEX mesh. At 4 weeks, scores were similar between mesh implant types, with implant material fibers embedded within bands of new fibrous connective tissue, and macrophages and multinucleated giant cells being the predominant inflammatory cell types at most sites, and these were associated with increased inflammatory responses in the implant. At 4 weeks, there were fewer overall multinucleated giant cells and more polymorphonucleated cells in response to PBS material fibers than in response to GalaFLEX fibers, and there was generally less angiogenesis in the PBS sites than in the P4HB sites.
[0184] PBS implant sites contained implant material consisting of approximately circular, elliptical, or elongated cross-sections through the fibers of transparent, refractive, and birefringent material arranged in numerous small clusters aligned parallel to the skin surface (see Figures 2 and 3). The implant material fibers had a fine granular texture. The implant material fibers were surrounded and separated by peri-implant tissue. The peri-implant tissue consisted of small foci of mature collagen (grade 1) and a continuous slightly thick to thick band of mostly immature collagen (grade 4) with moderate vascularization. A continuous layer 1-3 cells thick consisting of macrophages (moderate) and multinucleated giant cells (minimal to mild) lined the surface of the implant fibers embedded within the fibrous connective tissue bands. The new fibrous connective tissue was infiltrated by a variety of inflammatory cells including scattered or small aggregates of macrophages, multinucleated giant cells, polymorphonuclear cells (minimal to moderate), lymphocytes (minimal), and plasma cells (minimal). Minimal necrosis or apoptosis of inflammatory cells was an expected finding at sites of inflammation.
[0185] Irritant Rank for comparison mesh (GalaFLEX mesh) Based on the scores, the PBS test article was considered to be non-irritating, and the PBS mesh was considered to be biocompatible. Example 16 Determination of strength retention of PBS suture fibers and their local tissue response
[0186] Oriented monofilament fiber samples (0.109 ± 0.004 mm) made from PBS (USP suture size 6 / 0) were implanted into the dorsal subcutaneous tissue of New Zealand White rabbits to evaluate local tissue response and changes in fiber mechanical properties over time in vivo. Three male New Zealand White (NZW) rabbits were implanted with three mechanical test articles (9 in) and one histology / SEM test article (9 in) per animal.
[0187] Prior to implantation, rabbits (weighing at least 3.5 kg at the time of implantation) were anesthetized by intramuscular injection and subsequently maintained with isoflurane. Following anesthesia, animals were given a subcutaneous injection of analgesic. The surgical site was prepared for implantation. An incision was made cranially through the skin and a long forceps was passed through the subcutaneous tissue parallel to the spine and exiting caudally through a second skin incision. A single suture fiber was grasped with the forceps and pulled back into the tissue. This process was repeated for each fiber implantation. Each animal was implanted with four test PBS suture fibers (three mechanical specimens and one histology / SEM specimen) and four control monofilament fibers made from poly-4-hydroxybutyrate (TephaFLEX monofilament suture, Tepha Inc., Lexington, MA) on each side for a total of eight specimens per animal. The skin was closed and bandages applied. Animals were returned to their cages and monitored for recovery from anesthesia and subsequently monitored daily for general health.
[0188] All three rabbits were euthanized at 4 weeks. The skin was everted and the subcutaneous tissue was examined and the area around each implant was dissected free. The embedded sutures were retrieved by dissection from the surrounding tissue. The explants were processed for histological, biomechanical, and polymer testing. The retrieved sutures (n=9) were tested for tensile mechanical properties. Other samples (n=3) were designated for histopathology.
[0189] Analysis of local tissue reactions by histopathology demonstrated that the PBS suture was graded as non-irritating versus a comparative poly-4-hydroxybutyrate (TephaFLEX) suture control.
[0190] Tensile tests were performed on a universal testing machine operating on the principle of constant rate of extension of the test specimen. The tensile testing machine was equipped with pneumatic fiber grips and the preload was set at 0.05 kg. The gauge length was 138 mm and the strain rate was 300 mm / min. The location of break was recorded during the test.
[0191] After mechanical testing, a portion of the suture residue was removed and analyzed by gel permeation chromatography (GPC) to determine the weight average molecular weight (M w ) was measured. Mw was measured against monodisperse polystyrene standards using a TOSOH HPLC equipped with a refractive index detector as described above for the meshes. The test results are summarized in Table 13. The results shown in Table 13 indicate that the PBS monofilament suture retained 92.7% of its initial weight average molecular weight at 4 weeks after implantation, indicating that the suture begins to degrade in vivo but can retain substantial strength over the critical wound healing period. [Table 13]
[0192] Subcutaneously implanted oriented PBS monofilament suture fibers were analyzed by SEM after 4 weeks of implantation. SEM images were compared to unimplanted PBS suture fibers. SEM images were recorded at 400x magnification. An SEM image of the oriented PBS suture fibers before implantation is shown in Figure 4. An SEM image of the oriented PBS suture fibers after 4 weeks of subcutaneous implantation is shown in Figure 5. Surprisingly, there is no evidence of surface erosion of the implanted PBS suture fibers after 4 weeks in vivo. The SEM image in Figure 5 shows no evidence of surface erosion of the fibers. (Example 17) Preparation of poly(butylene succinate) mesh sutures
[0193] Mesh sutures were prepared from high strength monofilament PBS fibers using triaxial braiding. Wound monofilament fibers composed of succinic acid-1,4-butanediol-malic acid copolyester extruded and oriented as described in Example 2 were unwound and wound onto a braider bobbin. The bobbins were then loaded onto Herzog 4, 8, 16, and 24 carrier braiders. The wound monofilament fibers were further used as the axial fibers of mesh sutures. The monofilament fibers were unwound and threaded through the hollow shaft of a horn gear, and all bobbin and axial fiber ends were pulled through a braid ring to form a fell point. The braider bobbin was moved along the braid track and the braid helix angle was adjusted to 15° with a pick rate of 1-2 picks per inch (PPI). The construction (number of carriers and axial fibers used to prepare the hollow braid) and properties of triaxial braided mesh sutures prepared with 100 μm, 150 μm, and 200 μm P4HB monofilament fibers are shown in Tables 14, 15, and 16. The tables show the outer diameter (OD) and inner diameter (ID) of the mesh suture hollow braid. The width and thickness of the ply were measured after squashing the hollow blade flat. [Table 14] [Table 15] [Table 16] (Example 18) 3D printing of PBS-malic acid copolymer implants by melt extrusion deposition (MED) method
[0194] PBS-malic acid copolymer implants were printed by the MED method using an apparatus with a horizontal extruder feeding into a vertical extruder fitted with a vertical plunger and a movable stage. PBS-Malic Acid Copolymer pellets (160 kDa by GPC against polystyrene standards) were charged. The pellets were kept dry in the hopper by purging dry air through the silica bed. The temperature profile of the horizontal extruder was set at approximately 30°C in the build chamber with the temperatures of transition zone 1, zone 2, and zone 3 (extrusion zones) for the various tests as shown in Table 17. The residence time of the polymer in the MED horizontal extruder was approximately 22 min / cm. 3 The diameter of the nozzle orifice of the vertical extruder was 0.2 mm, and the drop printing frequency was about 50 drops / sec at the edge of the printed construct and about 240 drops / sec at the infill. Under these conditions, it was possible to print implants made from PBS-malic acid copolymer with good print quality. The weight average molecular weight Mw of the printed implants was measured by GPC and is also shown in Table 17. The Mw and polydispersity (PDI) were found to vary depending on the extrusion conditions used. As can be seen from Table 17, the weight average molecular weight of the printed implants increased with increasing temperature from 180°C to 220°C. [Table 17] The present invention provides, for example, the following items. (Item 1) A multifilament yarn or monofilament fiber derived from a polymer composition, wherein (a) the polymer composition comprises 1,4-butanediol units and succinic acid units, and is optionally isotopically enriched; (b) the multifilament yarn has one or more properties selected from the group consisting of a tensile strength greater than 4 g / denier but less than 14 g / denier, an elongation to break of 15% to 50%, and a denier per filament of 1 to 10; (c) the monofilament fiber has one or more properties selected from the group consisting of a tensile strength of 400 MPa to 1200 MPa, a Young's modulus of less than 3.0 GPa, and an elongation to break of 10% to 50%; and (d) optionally, (i) the weight average molecular weight of the polymer composition decreases in vivo under physiological conditions by 5% to 15% over a period of 4 to 8 weeks, or by 20% to 35% over a period of 12 weeks, or (ii) the percentage mass loss is greater than or equal to 10% in vivo under physiological conditions. 0%-5% over a 4 week period in vivo; or (iii) following implantation, said fiber has a strength retention of at least 80% at 4 weeks, or at least 65% at 12 weeks. (Item 2) A knitted or woven mesh, said mesh being knitted or woven from multifilament yarns or monofilament fibers, said multifilament yarns or monofilament fibers being knitted or woven from said multifilament yarns or monofilament fibers. A knitted or woven mesh, wherein the filament fibers are derived from a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, and when the mesh is incubated in phosphate buffered saline at 37° C., (i) the weight average molecular weight of the polymer composition decreases by 3% to 15% over a 4 week period, (ii) the weight average molecular weight of the polymer composition decreases by 5% to 15% over a 8 week period, (iii) the weight average molecular weight of the polymer composition decreases by 10% to 30% over a 12 week period, (iv) the mesh experiences a percentage mass loss of 0% to 5% over a 4 week period, or (v) the mesh experiences a percentage mass loss of 0% to 5% over a 8 week period. (Item 3) 3. The yarn, fiber, or mesh of claim 1 or 2, wherein the polymer composition (i) does not contain urethane linkages; (ii) is not prepared with a diisocyanate; (iii) contains 1 to 500 ppm of one or more, or all of the following: silicon, titanium, and zinc; (iv) does not contain tin; or (v) is not a blend of two or more polymers. (Item 4) 4. The yarn, fiber, or mesh of any one of the preceding claims, wherein the fiber has a Young's Modulus of at least 600 MPa, at least 1 GPa, or at least 2 GPa, but less than 3 GPa. (Item 5) 5. The yarn, fiber, or mesh according to any one of the preceding claims, wherein the polymer composition has a melting temperature of from 100°C to 150°C, or from 105°C to 120°C. (Item 6) 6. The yarn, fiber, or mesh of any one of the preceding claims, wherein (a) the polymer composition further comprises one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) the polymer composition further comprises one or more of the following: a branching agent, a crosslinking agent, a chain extender, and a reactive blending agent; or (c) the polymer composition further comprises a hydroxycarboxylic acid unit, optionally having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups. (Item 7) 7. The yarn, fiber, or mesh of claim 6, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid. (Item 8) 5. The yarn, fiber, or mesh of any one of the preceding claims, wherein the polymer composition comprises succinic acid-1,4-butanediol-malic acid copolyesters, succinic acid-1,4-butanediol-citric acid copolyesters, succinic acid-1,4-butanediol-tartaric acid copolyesters, succinic acid-1,4-butanediol-malic acid copolyesters further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyesters, succinic acid-adipic acid-1,4-butanediol-citric acid copolyesters, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyesters, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyesters further comprising citric acid, tartaric acid, or a combination thereof. (Item 9) 5. The fiber according to any one of claims 1 to 4, wherein the tensile strength of the fiber is greater than 500 MPa, 600 MPa, 700 MPa, or 800 MPa, but less than 2,000 MPa. Wisdom. (Item 10) 5. The yarn, fiber, or mesh of any one of the preceding claims, wherein the weight average molecular weight of the multifilament yarn or monofilament fiber is 80% or more, or 85% or more, of the weight average molecular weight of the polymer composition used to prepare the multifilament yarn or monofilament fiber. (Item 11) 11. The yarn, fiber, or mesh of any one of the preceding claims, wherein the multifilament yarn or monofilament fiber is produced by a process comprising the steps of: (a) spinning a multifilament yarn or monofilament fiber comprising the polymer composition; (b) drawing the multifilament yarn or monofilament fiber in one or more stages at an orientation ratio of at least 3.0 and a temperature of 50-70°C; (c) drawing the multifilament yarn or monofilament fiber in one or more stages at an orientation ratio of at least 2.0 and a temperature of 65-75°C; and (d) drawing the multifilament yarn or monofilament fiber at an orientation ratio of greater than 1.0 and a temperature of 70-75°C. (Item 12) Item 12. The multifilament yarn or monofilament fiber of item 11, wherein the order of steps is (a), (b), (c), and (d). (Item 13) 12. The multifilament yarn or monofilament fiber according to item 11, which is drawn in a conductive liquid chamber. (Item 14) 12. The multifilament yarn or monofilament fiber of item 11, further comprising a step of quenching the spun multifilament yarn or monofilament fiber in a conductive liquid chamber at a temperature of 50-70° C. prior to drawing. (Item 15) 12. The multifilament yarn or monofilament fiber of claim 11, further comprising the step of cooling the yarn or fiber by passing it between two godets after quenching. (Item 16) 12. The multifilament yarn or monofilament fiber according to item 11, which is spun at a temperature range of 60 to 230°C, 80 to 180°C, 80 to 175°C, or 80 to 170°C. (Item 17) 17. A method of forming a yarn or fiber according to any one of the preceding claims, wherein the yarn or fiber is produced by a process comprising the steps of: (a) spinning a polymer composition comprising 1,4-butanediol units and succinic acid units to form a multifilament yarn or monofilament fiber comprising the polymer composition; (b) drawing the multifilament yarn or monofilament fiber in one or more stages at an orientation ratio of at least 3.0 and a temperature of 50-70°C; (c) drawing the multifilament yarn or monofilament fiber in one or more stages at an orientation ratio of at least 2.0 and a temperature of 65-75°C; and (d) drawing the multifilament yarn or monofilament fiber at an orientation ratio of greater than 1.0 and a temperature of 70-75°C. (Item 18) 18. The method of claim 17, wherein the multifilament yarn or monofilament fiber is stretched in a conductive liquid chamber. (Item 19) The spun multifilament yarn or monofilament fiber is placed in a water bath for 50 18. The method of claim 17, further comprising the step of quenching before drawing at a temperature of ∼70°C, and / or the step of cooling the yarn or fiber after quenching by passing it between two godets, and / or the step of drying the polymer composition before spinning to a moisture content of the polymer composition of less than 0.1 wt%, less than 0.05 wt%, or less than 0.005 wt%. (Item 20) Item 18. The method according to item 17, wherein the multifilament yarn or monofilament fiber is spun at a temperature range of 60 to 230°C, 80 to 180°C, 80 to 175°C, or 80 to 170°C. (Item 21) Item 18. The method according to item 17, wherein (a) the spun multifilament yarn or monofilament fiber is not quenched or not cold-stretched, or (b) the sum of the orientation ratios is greater than 6.0, 6.5, 7.0, 7.5, or 8.0, and the multifilament fiber or monofilament fiber is stretched at a temperature of 50°C to 90°C. (Item 22) 1. An implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the implant comprising the polymer composition in an oriented form, and optionally the polymer composition being isotopically enriched. (Item 23) 23. The implant of item 22, wherein the oriented form comprises a fiber, a mesh, a woven fabric, a nonwoven fabric, a film, a molding, a patch, a tube, a laminate, or a pultruded profile. (Item 24) 24. The implant of claim 23, wherein the fiber is monofilament, multifilament, braided, or barbed. (Item 25) Item 26. The implant according to item 23, wherein the mesh, woven or non-woven form is a knitted mesh, a woven mesh, a monofilament mesh, or a multifilament mesh. Item 27. The implant according to item 22, wherein the oriented configuration is uniaxially or biaxially oriented. 1. An implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the implant having a degradation rate under physiological conditions, wherein the weight average molecular weight of the polymer composition decreases by 3% to 15% over a 4 week period in vivo, or the weight average molecular weight of the polymer composition decreases by 10% to 30% over a 12 week period in vivo. (Item 28) 1. An implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the implant having a degradation rate such that when the implant is incubated in phosphate buffered saline at 37° C., (i) the weight average molecular weight of the polymer composition decreases by 3% to 13% over a 4 week period, (ii) the weight average molecular weight of the polymer composition decreases by 5% to 15% over a 8 week period, (iii) the weight average molecular weight of the polymer composition decreases by 10% to 30% over a 12 week period, (iv) the implant experiences a percentage mass loss of 0% to 5% over a 4 week period, or (v) the implant experiences a percentage mass loss of 0% to 5% over a 8 week period. (Item 29) 1. An implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, wherein the implant has a strength retention of greater than 75% at 4 weeks after implantation or greater than 65% at 12 weeks after implantation. (Item 30) 30. The implant according to any one of items 22 and 27 to 29, which is porous. (Item 31) 30. The implant according to any one of items 27 to 29, wherein the polymer composition is partially or completely oriented. (Item 32) 32. The implant according to item 31, comprising partially or fully oriented monofilament or multifilament fibers. (Item 33) 33. The implant according to items 24 and 32, wherein the tensile strength of the fibers is 400 MPa to 1,200 MPa, 500 MPa to 1,200 MPa, 600 MPa to 1,200 MPa, or 700 MPa to 1,200 MPa. (Item 34) 34. The implant according to items 32 and 33, wherein the fibers have a Young's modulus of at least 600 MPa, 800 MPa, 1 GPa, and 2 GPa, but less than 3 GPa. (Item 35) 33. The implant according to item 32, wherein the fibers are knitted or woven into a mesh. (Item 36) 36. The implant according to any one of items 23, 24, and 35, wherein (a) the mesh has a burst strength of 1 kgf to 100 kgf, or 10 kgf to 30 kgf, or (b) the Taber stiffness of the mesh is 0.01 to 10 Taber stiffness units, or 0.1 to 1 Taber stiffness units. (Item 37) 30. The implant according to any one of items 22 and 27 to 29, wherein (a) the surface of the implant does not become indented during degradation under physiological conditions in vivo for a period of 4 weeks; or (b) when implanted, the dimensions of the implant do not shrink by more than 5% of their initial value under physiological conditions in vivo for a period of 4 weeks. (Item 38) 30. The implant of any one of items 22 and 27 to 29, derived from a polymer composition further comprising: (a) one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) one or more of the following: a branching agent, a crosslinking agent, a chain extender, and a reactive blending agent; or (c) a hydroxycarboxylic acid unit, optionally having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups. (Item 39) 39. The implant of claim 38, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid. (Item 40) succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-citric acid copolyester, succinic acid-1,4-butanediol-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-citric acid copolyester, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyester, or succinic acid- 30. An implant according to any one of items 22 and 27 to 29, derived from a polymer composition comprising an adipic acid-1,4-butanediol-malic acid copolyester. (Item 41) 30. The implant of any one of items 22 and 27 to 29, further comprising a plasticizer, a nucleating agent, a coating, a dye, a medical marker, a bioactive agent, a therapeutic agent, a diagnostic agent, a prophylactic agent, a contrast agent, a radiopaque marker, a radioactive material, an anti-adhesion agent, hyaluronic acid, an antibiotic, rifampin, minocycline, collagen, hydroxyapatite, or an absorbable polymer comprising one or more of the following monomers: glycolic acid, lactic acid, trimethylene carbonate, p-dioxanone, ε-caprolactone, 4-hydroxybutyric acid, and 3-hydroxybutyric acid. (Item 42) 42. The implant according to any one of items 22 to 41, wherein the polymer composition (i) does not contain urethane linkages, (ii) is not prepared with diisocyanates, (iii) contains 1 to 500 ppm of one or more, or all of the following: silicon, titanium, and zinc, (iv) does not contain tin, or (v) is not a blend of two or more polymers. (Item 43) 43. The implant according to any one of items 22 to 42, wherein the polymer composition has a melting temperature of 100°C to 150°C, or 105°C to 120°C. (Item 44) Sutures, barbed sutures, monofilament sutures, braided sutures, mesh sutures, wound closure devices, patches, wound healing devices, wound dressings, burn dressings, ulcer dressings, skin replacement materials, hemostatic materials, tracheal reconstruction devices, organ retrieval devices, dural patches or dural replacements, devices for nerve regeneration or repair, hernia repair devices, hernia repair meshes, hernia plugs, inguinal hernia plugs, devices for temporary wound or tissue support, scaffolds for tissue engineering, guided tissue repair / regeneration devices, anti-adhesion membranes or barriers, tissue isolation membranes, retention Sustainers, slings, pelvic floor reconstruction devices, devices for the treatment of pelvic organ prolapse, urethral suspension devices, devices for the treatment of urinary incontinence, devices for the treatment of stress urinary incontinence, bladder repair devices, expansion or filling devices, bone marrow scaffolds, bone plates, implant fixation devices, ligament repair or strengthening devices, anterior cruciate ligament repair devices, tendon repair or strengthening devices, rotator cuff repair devices, meniscus repair or regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, cardiovascular patches , catheter balloons, vascular closure devices, intracardiac septal defect repair devices including but not limited to atrial septal defect repair devices and PFO (patent foramen ovale) closure devices, left atrial appendage (LAA) closure devices, pericardial patches, venous valves, heart valves, vascular grafts, myocardial regeneration devices, periodontal meshes, guided tissue regeneration membranes for periodontal tissue, ophthalmic cell implants, imaging devices, cochlear implants, anastomosis devices, cell seeding devices, cell encapsulation devices, controlled release devices, drug delivery devices, plastic surgery devices, breast lift devices, mastopexy devices devices for breast reconstruction, devices for breast enlargement, devices for breast reduction, breast implants, devices for the removal, reshaping and reorientation of breast tissue, devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift, devices for eyelid lift, devices for face lift, devices for wrinkle removal, devices for thread lift, devices for lifting and supporting sagging areas of the face, eyebrows and neck, devices for rhinoplasty, devices for cheekbone enhancement, devices for earplasty, devices for neck lift,The implant according to any one of items 22, 27 to 29 and 36, which is selected from the group of devices for genioplasty, devices for buttock lift, devices for cosmetic repair and devices for facial scar correction. (Item 45) The implant is a braided suture comprising oriented multifilament fibers, 45. The implant of item 44, wherein the braided suture has a breaking strength of 40N to 270N, and optionally wherein the suture has a strength retention of at least 40% under physiological conditions in vivo at 4 to 6 months. (Item 46) 46. The implant of any one of items 22 to 45, comprising less than 20 endotoxin units per implant as determined by Limulus Amebocyte Lysate (LAL) assay. (Item 47) 45. A method for making the implant according to any one of claims 22, 27 to 29 and 44, wherein the polymer composition comprises 1,4-butanediol units and succinic acid units, the method comprising the steps of providing the polymer composition and performing a process comprising casting, solvent casting, solution spinning, solution joining of fibers, melt processing, extrusion, melt extrusion, melt spinning, fiber spinning, orientation, relaxation, annealing, injection molding, compression molding, lamination, dry spinning, knitting, weaving, crocheting, melt blowing, film forming, film blowing, film casting, membrane forming, electrospinning, thermoforming, pultrusion, centrifugal spinning, molding, tube extrusion, spunbonding, nonwoven fabric production, spunbonding ... forming or incorporating the polymer composition into an implant by one or more processes including staple fiber entanglement, fiber knitting, weaving, and crocheting, mesh making, coating, dip coating, laser cutting, barb forming, punching, perforating, hole forming, freeze drying, stitching, calendaring, lyophilization, phase separation, particle leaching, thermal phase separation, leaching, latex processing, gas plasma treatment, emulsion processing, 3D printing, fused filament manufacturing, fused pellet deposition, melt extrusion deposition, selective laser melting, printing of slurries and solutions using a coagulation bath, or printing using a binding solution and powder granules. (Item 48) 1. A method of promoting healing of a wound, injury, or defect at a patient site or repairing or regenerating tissue at a patient site, comprising administering to the site an implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the implant comprising: (a) the polymer composition in an oriented form; (b) a degradation rate under physiological conditions such that the weight average molecular weight of the polymer composition decreases by 3% to 15% over a four week period or the weight average molecular weight of the polymer composition decreases by 20% to 35% over a twelve week period; and (c) the wherein, when the implant is incubated in phosphate buffered saline at 37° C., (i) the weight average molecular weight of the polymer composition decreases by 3% to 13% over a 4 week period, (ii) the weight average molecular weight of the polymer composition decreases by 5% to 15% over an 8 week period, (iii) the implant has a percentage mass loss of 0% to 5% over a 4 week period, or (iv) the implant has a percentage mass loss of 0% to 5% over an 8 week period, or (d) has a strength retention of greater than 75% at 4 weeks after implantation or greater than 65% at 12 weeks after implantation. (Item 49) 1. A surgical mesh implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the composition optionally being isotopically enriched, (a) the weight average molecular weight of the polymer composition decreases by 3% to 15% over a 4 week period, or by 20% to 35% over a 12 week period, or by a percentage mass loss of 0% to 5% over a 12 week period, in vivo under physiological conditions, or (b) the burst strength of the implant decreases by less than 20% in 4 weeks, or by less than 35% in 12 weeks, and (c) the implant is optionally sterile. (Item 50) Below:(i)5~800g / m 2 (ii) a suture pull-out strength of at least 10 N, or at least 20 N; (iii) a suture pull-out strength of at least 10 μm, at least 50 μm, or pores having a diameter of at least 100 μm; (iv) a burst strength of greater than 0.1 kPa; (v) a Taber stiffness of at least 0.01 Taber stiffness units; (vi) knitted, woven, crocheted, or braided fibers; (vii) monofilament fibers; (viii) multifilament fibers; and (ix) a degradation rate in phosphate buffered saline at 37° C. such that the weight average molecular weight of the mesh decreases by 10% to 30% over a 12 week period. (Item 51) 51. The implant of item 50, wherein the fibers have one or more of the following properties: (i) orientation, (ii) tensile strength of 400 MPa to 1,200 MPa, (iii) tensile strength of 4 g / denier to 12 g / denier, (iv) Young's modulus of 600 MPa to 3.0 GPa, (v) elongation at break of 10% to 50%, (vi) diameter of 10 μm to 1 mm, (vii) melting temperature of 100 to 150° C. or 105° C. to 120° C., and (viii) a degradation rate in phosphate buffered saline at 37° C. such that the weight average molecular weight of the fibers decreases by 10% to 25% over a period of 12 weeks. (Item 52) 1. A surgical mesh implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the mesh comprising fibers, the implant having a burst strength of greater than 0.1 kPa, and the fibers having a Young's Modulus of at least 600 MPa, at least 1 GPa, or at least 2 GPa. (Item 53) 53. The implant of claim 52, wherein (a) the fibers have one or more of the following properties: a tensile strength of 400 MPa to 1,200 MPa, a tensile strength of 4 g / denier to 12 g / denier, a Young's modulus less than 3.0 GPa, an elongation at break of 10% to 50%, a diameter of 10 μm to 1 mm, a melt temperature of 100 to 150° C. or 105° C. to 120° C.; or (b) the fibers are prepared by melt extrusion from the polymer composition, and the weight average molecular weight of the extruded fibers is 80% or more, or 85% or more of the weight average molecular weight of the polymer composition before extrusion. (Item 54) The mesh has the following characteristics: 5 to 800 g / m 2 53. The implant of claim 52, having one or more of: an areal density of at least 10 N, or at least 20 N; a suture pull-out strength of at least 10 N; and pores having a diameter of at least 10 μm, at least 50 μm, or at least 100 μm. (Item 55) 53. The implant of item 52, wherein the monofilament fibers are stretched to orient the fibers and increase the stiffness of the mesh, the Young's Modulus of the fibers being at least 600 MPa, at least 800 MPa, or at least 1 GPa, and optionally the fibers having a diameter of 10 μm to 1 mm. (Item 56) 56. The implant of item 55, wherein the fibers have a Young's Modulus of less than 3 GPa, or the fibers have a Young's Modulus of more than 1.5 GPa or 2.0 GPa but less than 3 GPa. (Item 57) 56. The implant according to items 52 and 55, wherein the fibers are oriented with an orientation ratio of at least 6.0, at least 6.5, or at least 7.0. (Item 58) A surgical mesh implant comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the mesh comprising fibers, the fibers comprising the polymer composition, the steps of: spinning a multifilament or monofilament fiber, the multifilament or monofilament fiber being spun into at least 6 or 8, and at a temperature of 50-80°C, in one or more stages. (Item 59) 59. The surgical mesh according to item 58, wherein the fibers are first stretched in one or more stages with a minimum orientation ratio of 3 to 4 and a temperature of 50 to 70°C, then hot stretched in one or more stages with a minimum orientation ratio of 2 to 3 and a temperature of 60 to 80°C, and then hot stretched in one or more stages with an orientation ratio greater than 1.0 and a temperature of 70 to 80°C. (Item 60) 60. The surgical mesh of claims 58 and 59, wherein the fibers are prepared by one or more of the following steps: (i) drying the polymer composition prior to melt spinning to a water content of the polymer composition of less than 0.1 wt%, less than 0.05 wt%, or less than 0.005 wt%, and (ii) hot drawing the fibers in a heated conductive liquid chamber. (Item 61) 59. The implant of any one of items 49, 52, 55, and 58, wherein the polymer composition used to prepare the implant further comprises: (a) one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) optionally one or more of the following, excluding diisocyanate agents and agents that incorporate urethane linkages in the polymer composition: a branching agent, a crosslinking agent, a chain extender, and a reactive blending agent; (c) optionally a hydroxycarboxylic acid unit having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups. (Item 62) 62. The polymer composition of claim 61, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid. (Item 63) 59. The implant according to any one of items 49, 52, 55, and 58, wherein the polymer composition used to prepare the implant comprises succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-citric acid copolyester, succinic acid-1,4-butanediol-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-citric acid copolyester, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyester, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof. (Item 64) 64. The polymer composition according to any one of items 59 to 63, which (i) does not contain urethane linkages, (ii) is not prepared with diisocyanates, (iii) contains 1 to 500 ppm of one or more, or all of the following: silicon, titanium, and zinc, (iv) does not contain tin, or (v) is not a blend of two or more polymers. (Item 65) 65. The polymer composition according to any one of items 49 to 64, having a melting temperature of 100 ° C to 150 ° C, or 105 ° C to 120 ° C. (Item 66) (a) the surgical mesh is a knitted mesh, a woven mesh, a crocheted mesh, a monofilament mesh, a multifilament mesh, a weft knit mesh, a warp knit mesh, a plug, a hernia plug, a void filler, an inguinal hernia plug, having a three-dimensional shape that can be temporarily deformed as needed or has an outwardly curving exterior and an inwardly curving interior; (b) said surgical mesh further comprises an anti-adhesion layer, barbs, hooks, self-anchoring tips, microgrips, fleece, reinforcing materials, and reinforced outer edges or borders; or (c) said surgical mesh further comprises a plasticizer, a nucleating agent, a coating, a tubing ... 59. The implant of any one of items 49, 52, 55, and 58, further comprising a marker, dye, medical marker, bioactive agent, therapeutic agent, diagnostic agent, prophylactic agent, contrast agent, radiopaque marker, radioactive material, anti-adhesion agent, hyaluronic acid, antibiotic, rifampin, minocycline, collagen, hydroxyapatite, or an absorbable polymer comprising one or more of the following monomers: glycolic acid, lactic acid, trimethylene carbonate, p-dioxanone, ε-caprolactone, 4-hydroxybutyric acid, and 3-hydroxybutyric acid. (Item 67) The implant is selected from the group consisting of wound closure devices, patches, wound healing devices, devices for tissue or suture reinforcement, tracheal reconstruction devices, organ retrieval devices, dural patches or replacements, devices for nerve regeneration or repair, hernia repair devices, hernia meshes, hernia plugs, inguinal hernia plugs, devices for temporary wound or tissue support, tissue engineering scaffolds, guided tissue repair / regeneration devices, anti-adhesion membranes or barriers, tissue isolation membranes, retention membranes, slings, devices for pelvic floor reconstruction, devices for the treatment of pelvic organ prolapse. , urethral suspension devices, devices for the treatment of urinary incontinence, bladder repair devices, void filling devices, bone marrow scaffolds, ligament repair or strengthening devices, anterior cruciate ligament repair devices, tendon repair or strengthening devices, rotator cuff repair devices, meniscus repair or regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, cardiovascular patches, vascular closure devices, intracardiac septal defect repair devices, atrial septal defect repair devices, patent foramen ovale closure devices, left atrial appendage closure devices, pericardial patches, vascular grafts, cardiac Muscle regeneration devices, periodontal meshes, guided tissue regeneration membranes for periodontal tissue, imaging devices, anastomosis devices, devices for cell seeding, devices for controlled release, devices for drug delivery, plastic surgery devices, devices for breast lift, devices for mastopexy, devices for breast reconstruction, devices for breast enlargement, breast implants, devices for breast reduction, devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift, devices for eyelid lift, devices for face lift, devices for rhytidectomy, devices for rhinoplasty devices, devices for cheekbone augmentation, devices for otoplasty, devices for neck lift, devices for chinplasty, devices for buttock lift, devices for cosmetic repair, devices for facial scar correction, pouches, holders, covers, housings or casings which partially or completely encase, surround or hold implantable medical devices, cardiac rhythm management devices, pacemakers, defibrillators, generators, implantable access systems, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medicines and fluids, intrathecal delivery systems, pain pumps,or a device that provides a drug or electrical stimulation to the body. (Item 68) Item 69: A method of making the surgical mesh implant of any one of items 59, 52, 55, 61-67, wherein the mesh comprises fibers, the method comprising the steps of melt spinning fibers comprising the polymer composition, quenching the extruded fibers, heating the fibers, and drawing the fibers in multiple stages. (ii) quenching the extruded fiber in a water bath at a temperature between 40° C. and 70° C.; (iii) cooling the extruded fiber after quenching without stretching; (iv) drawing the cooled extruded fiber in a conductive liquid chamber to an orientation ratio of at least 3.0 at a temperature between 50° C. and 70° C.; and (v) one or more further (v) drawing the extruded fiber in a conductive liquid chamber at a temperature between 60 and 80° C. after the initial drawing; (v) drawing the extruded fiber in multiple stages at gradually increasing temperatures; (vi) drawing the extruded fiber in a conductive liquid chamber at multiple stages at gradually increasing temperatures; (vii) drawing the fiber without the use of a heated oven; (viii) extruding the fiber at a temperature between 80° C. and 180° C.; (ix) extruding the fiber at a temperature below 230° C. or below 200° C.; (x) drying the polymer composition prior to melt spinning to a water content of the polymer composition below 0.1 wt %, below 0.05 wt %, or below 0.005 wt %. (Item 70) 69. The method of claim 68, wherein the polymer composition has a melting temperature of 100°C to 150°C, or 105°C to 120°C. (Item 71) 70. The method of claim 68, wherein the fibers are prepared by solvent spinning or 3D printing. (Item 72) 70. The method of claim 68, further comprising drying the polymer composition to a water content of the polymer composition of less than 0.1 wt%, less than 0.05 wt%, or less than 0.005 wt%. (Item 73) 71. A method of promoting healing of a wound, injury, or defect at a site on a patient, or repairing, lifting, or reconstructing tissue at a site on a patient, comprising administering to said site an implant according to any one of paragraphs 51 to 70. (Item 74) 74. The method of claim 73, comprising the step of delivering the implant by one or more of the following methods: a minimally invasive technique, a laparoscopic technique, temporary deformation of the implant, and insertion of the implant through an insertion tool. (Item 75) 74. The method of claim 73, wherein (a) the implant conforms to the patient's anatomy, (b) the implant does not curl at the edges after implantation, (c) the surface of the implant is free of indentations for a period of 4 weeks after administration of the implant to the site, and (d) the dimensions of the implant do not shrink by more than 5% from their initial values in any direction. (Item 76) The implant is used in hernia repair, inguinal hernia repair, femoral hernia repair, incisional hernia repair, ventral hernia repair, umbilical hernia repair, wound management, reinforcement, tracheal reconstruction, organ retrieval, dura repair, nerve regeneration or repair, tissue engineering, guided tissue repair or regeneration, anti-adhesion or tissue separation applications, sling surgery, pelvic floor reconstruction, urethral suspension, treatment of urinary incontinence, bladder repair, void filling, bone marrow replacement, ligament repair device or reinforcement, anterior cruciate ligament repair, tendon repair or reinforcement, rotator cuff repair, meniscus repair or regeneration, articular cartilage repair, osteochondral repair, spinal fixation, cardiovascular patching, blood vessel closure, intracardiac septal defect repair, atrial septal defect repair, patent foramen ovale closure, left atrial appendage closure, pericardial patching, vascular grafts, myocardial regeneration, guided tissue regeneration of periodontal tissue, 75. The method of items 73 and 74, for use in bioimaging, imaging, anastomosis, cell seeding, controlled release, drug delivery, plastic surgery, breast lift, mastopexy, breast reconstruction, breast augmentation, breast reduction, breast reconstruction after mastopexy with or without breast implants, facial reconstruction, forehead lift, brow lift, eyelid lift, face lift, rhytidectomy, rhinoplasty, cheekbone augmentation, otoplasty, neck lift, chinplasty, buttock lift, cosmetic repair, facial scar correction, and complete or partial encapsulation of implantable medical devices, cardiac rhythm management devices, pacemakers, defibrillators, generators, implantable access systems, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medicines and fluids, intrathecal delivery systems, pain pumps, or devices that provide drugs or electrical stimulation to the body. (Item 77) 1. A hernia repair mesh comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the mesh comprising monofilament fibers, multifilament fibers, or combinations thereof formed from the polymer composition, the mesh having a burst strength of 1 kgf to 100 kgf. (Item 78) 78. The hernia repair mesh according to item 77, wherein the mesh is coated with an anti-adhesion agent, optionally the anti-adhesion agent being hyaluronic acid or a derivative thereof. (Item 79) 1. A breast reconstruction mesh comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the mesh comprising monofilament fibers, multifilament fibers, or combinations thereof formed from the polymer composition, the mesh having a burst strength of 0.5 kgf to 50 kgf. (Item 80) 80. The mesh of item 79 which is a mesh for breast fixation, a mesh used in breast reconstruction after mastopexy, a mesh used for breast augmentation, a mesh used as a void filler, a pleated mesh, a mesh used as a scaffold, a mesh used as a scaffold for fat grafts, a mesh used with a tissue expander, or an expandable mesh. (Item 81) 80. The mesh according to items 77 and 79, which is porous. (Item 82) (b) the mesh is formed into a plug, a 3D shape, or is shaped to conform to or has the anatomical shape of a patient; (c) the mesh is capable of being temporarily deformed for minimally invasive delivery to a patient, and optionally the outer border of the mesh is reinforced so that the mesh can be deformed from its original shape for implantation and can regain its shape after placement in the patient; and (d) the mesh has a mass of 5 to 800 g / m 2 Item 82. The mesh of item 81, having an areal density of at least 10 N, or at least 20 N, a suture pull-out strength of at least 10 N, or at least 20 N, and one or more pores having a diameter of at least 10 μm, at least 50 μm, or at least 100 μm. (Item 83) Item 82. The mesh of item 81, further comprising barbs, fleece, hooks, self-fixating tips, anchoring devices, microgrips, tabs, attachment portions or straps, sutures with or without needles for securing the mesh to the patient's tissue. (Item 84) 82. The mesh of claim 81, wherein the fibers have one or more of the following properties: (i) orientation; (ii) a tensile strength of at least 400 MPa, 500 MPa, 600 MPa, or 700 MPa, but less than 1,200 MPa; (iii) a tensile strength of 4 g / denier to 12 g / denier; (iv) a Young's modulus of at least 600 MPa, 1 GPa, or 2 GPa, but less than 3 GPa; (v) an elongation at break of 10% to 50%; (vi) a diameter of 10 μm to 1 mm, or 50 μm to 500 μm; and (vii) a melting temperature of 100 to 150° C., or 105° C. to 120° C. (Item 85) 82. The mesh of item 81, wherein the weight average molecular weight of the polymer composition decreases by 3% to 15% over a 4 week period, or by 20% to 35% over a 12 week period. (Item 86) (i) the polymer composition, when incubated in phosphate buffered saline at 37° C. (ii) the weight average molecular weight of the polymer composition decreases by 3% to 13% over a 4 week period; (ii) the weight average molecular weight of the polymer composition decreases by 5% to 15% over a 8 week period; (iii) the weight average molecular weight of the polymer composition decreases by 10% to 30% over a 12 week period; (iv) the percentage mass loss of the mesh is between 0% and 5% over a 4 week period; or (v) the percentage mass loss of the mesh is between 0% and 5% over a 8 week period. (Item 87) 82. The mesh of item 81, wherein (a) after implantation, the burst strength of said mesh in vivo is greater than 80% at 4 weeks or greater than 65% at 12 weeks, and (b) after implantation, under physiological conditions, during degradation in vivo for a period of 4 weeks, there is no indentation of the mesh fiber surface. (Item 88) 82. The mesh of item 81, which after implantation retains 95% to 100% of its original surface area for 4 weeks in vivo under physiological conditions and, optionally, does not shrink by more than 5% in any direction during this period. (Item 89) 89. The mesh of any one of items 81 to 88, wherein the mesh is derived from a polymer composition, (a) the polymer composition further comprises one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) the polymer composition further comprises one or more of a branching agent, a crosslinking agent, a chain extender, and a reactive blending agent; or (c) the polymer composition further comprises a hydroxycarboxylic acid unit, optionally having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups. (Item 90) 90. The mesh of claim 89, wherein the branching, cross-linking, chain extending, or reactive blending agent is selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid. (Item 91) 91. The mesh according to any one of items 77 to 90, derived from a polymer composition comprising succinic acid-1,4-butanediol-malic acid copolyesters, succinic acid-1,4-butanediol-citric acid copolyesters, succinic acid-1,4-butanediol-tartaric acid copolyesters, succinic acid-1,4-butanediol-malic acid copolyesters further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyesters, succinic acid-adipic acid-1,4-butanediol-citric acid copolyesters, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyesters, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyesters further comprising citric acid, tartaric acid, or a combination thereof. (Item 92) 92. The mesh according to any one of items 77 to 91, wherein the polymer composition (i) does not contain urethane linkages; (ii) is not prepared with a diisocyanate; (iii) contains 1 to 500 ppm of one or more elements selected from the group consisting of silicon, titanium, and zinc; (iv) does not contain tin; or (v) the polymer composition is not a blend of two or more polymers. (Item 93) 93. The mesh according to any one of items 77 to 92, having a melting temperature of 100°C to 150°C, or 105°C to 120°C. (Item 94) 94. The mesh according to any one of items 77 to 93, wherein the fibers are produced by a process comprising the steps of spinning a multifilament or monofilament fiber comprising the polymer composition, drawing the multifilament or monofilament fiber with an orientation ratio of at least 3 or 4 at a temperature of 50-70°C, then drawing the multifilament or monofilament fiber with an orientation ratio of at least 2 at a temperature of 65-75°C in one or more stages, then drawing the multifilament or monofilament fiber with an orientation ratio of more than 1.0 at a temperature of 70-75°C in one or more stages. (Item 95) 1. A sling device comprising a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the sling comprising a monofilament fiber, a multifilament fiber, or a combination thereof formed from the polymer composition. (Item 96) 96. The sling device of item 95 derived from a polymer composition further comprising one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid, branching agents, crosslinking agents, chain extenders, and reactive blending agents, optionally hydroxycarboxylic acid units having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, or two hydroxyl groups and two carboxyl groups. (Item 97) 98. The sling device of claim 96, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid. 96. The sling device according to item 95, derived from a polymer composition comprising succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-citric acid copolyester, succinic acid-1,4-butanediol-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-citric acid copolyester, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyester, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof. (Item 99) Item 96. The sling device of item 95, wherein the polymer composition (i) does not contain urethane linkages, (ii) is not prepared with a diisocyanate, or (iii) is not a blend of two or more polymers. (Item 100) Item 96. The sling device according to item 95, wherein the melting temperature of the polymer composition is from 100°C to 150°C, or from 105°C to 120°C. (Item 101) 101. The sling device according to any one of items 95 to 100, which is a urethral suspension device. (Item 102) The following characteristics: thickness 0.1-1mm, 100-300g / m 2 Fibers having an areal density of 0.01 mm, a pore size of 5 μm to 5 mm, a tensile strength of at least 400 MPa, 500 MPa, 600 MPa, or 700 MPa but less than 1,200 MPa, and an average diameter of 70 to 199 μm. 102. The sling device according to items 95 to 101, having one or more of the oriented fibers having an equal diameter. (Item 103) 1. An implant selected from the group consisting of a hernia mesh, a breast reconstruction mesh, a mastopexy device, and a sling device, said implant comprising a polymer composition, said polymer composition comprising 1,4-butanediol units and succinic acid units, said implant being formed by 3D printing.
Claims
1. 1. A knitted or woven mesh implant, said mesh being knitted or woven from monofilament fibers derived from a polymer composition, said polymer composition comprising 1,4-butanediol units and succinic acid units, optionally isotopically enriched, said monofilament fibers being oriented, having an elongation at break of 10% to 50%, and having one or more properties selected from the group consisting of a tensile strength of 400 MPa to 1200 MPa, and a Young's modulus of less than 3.0 GPa, and said polymer composition does not comprise urethane linkages and is not prepared with a diisocyanate.
2. 10. The knitted or woven mesh implant of claim 1, wherein when the mesh is incubated in phosphate buffered saline at 37°C, (i) the weight average molecular weight of the polymer composition decreases by 3% to 15% over a 4 week period, (ii) the weight average molecular weight of the polymer composition decreases by 5% to 15% over a 8 week period, (iii) the weight average molecular weight of the polymer composition decreases by 10% to 30% over a 12 week period, (iv) the mesh experiences a percentage mass loss of 0% to 5% over a 4 week period, or (v) the mesh experiences a percentage mass loss of 0% to 5% over a 8 week period.
3. 3. The knitted or woven mesh implant of claim 1 or 2, wherein the polymer composition (i) contains 1-500 ppm of one or more, or all of the following: silicon, titanium, and zinc; (ii) contains no tin; or (iii) is not a blend of two or more polymers.
4. 4. The knitted or woven mesh implant of any one of claims 1 to 3, wherein the Young's Modulus of the fibers is at least 600 MPa, at least 1 GPa, or at least 2 GPa, but less than 3 GPa.
5. The knitted or woven mesh implant of any one of claims 1 to 4, wherein the polymer composition has a melting temperature of from 100°C to 150°C, or from 105°C to 120°C.
6. (a) the polymer composition further comprises one or more of the following: second diacid units, second diol units, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) the polymer composition further comprises one or more of the following: a branching agent, a crosslinking agent, a chain extender, and a reactive blending agent; or (c) the knitted or woven mesh implant of any one of claims 1 to 5, wherein the polymer composition further comprises a hydroxycarboxylic acid unit having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups.
7. 7. The knitted or woven mesh implant of claim 6, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid.
8. 5. The knitted or woven mesh implant of any one of claims 1 to 4, wherein the polymer composition comprises succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-citric acid copolyester, succinic acid-1,4-butanediol-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-citric acid copolyester, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyester, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof.
9. 5. The knitted or woven mesh implant of any one of claims 1 to 4, wherein the fibers have a tensile strength of greater than 500 MPa, 600 MPa, 700 MPa, or 800 MPa, but less than 2,000 MPa.
10. The knitted or woven mesh implant of any one of claims 1 to 4, wherein the polymer composition has a weight average molecular weight of 75,000 to 300,000.
11. A method for producing a knitted or woven mesh implant according to any one of claims 1 to 9, comprising the steps of producing the fiber by a process comprising the steps of: (a) spinning a monofilament fiber comprising the polymer composition; (b) drawing the monofilament fiber in one or more stages at an orientation ratio of at least 3.0 and a temperature of 50-70°C; (c) drawing the monofilament fiber in one or more stages at an orientation ratio of at least 2.0 and a temperature of 65-75°C; and (d) drawing the monofilament fiber at an orientation ratio of greater than 1.0 and a temperature of 70-75°C.
12. 12. The method of claim 11, wherein the order of steps is (a), (b), (c), and (d).
13. The method of claim 11 , wherein the monofilament fiber is stretched in a chamber containing a thermally conductive liquid.
14. 12. The method of claim 11, further comprising quenching the spun monofilament fiber in a chamber containing a thermally conductive liquid at a temperature of 50-70°C before drawing.
15. The method of claim 11 , further comprising the step of cooling the fiber after quenching by passing it between two godets.
16. The method of claim 11, wherein the monofilament fiber is spun at a temperature range of 60 to 230°C, 80 to 180°C, 80 to 175°C, or 80 to 170°C.
17. 12. The method of claim 11, further comprising quenching the spun monofilament fiber in a water bath at a temperature of 50-70° C. before drawing, and / or cooling the fiber after quenching by passing it between two godets, and / or drying the polymer composition before spinning to a moisture content of the polymer composition of less than 0.1 wt %, less than 0.05 wt %, or less than 0.005 wt %.
18. 12. The method of claim 11, wherein: (a) the spun monofilament fiber is not quenched or cold stretched; or (b) the sum of the orientation ratios is greater than 6.0, 6.5, 7.0, 7.5, or 8.0, and the monofilament fiber is stretched at a temperature between 50° C. and 90° C.
19. A medical implant comprising a polymer composition, said polymer composition comprising 1,4-butanediol units and succinic acid units and having an endotoxin content of less than 2.5 EU / g, said implant comprising said polymer composition in an oriented form, and optionally said polymer composition being isotopically enriched; 1. A medical implant, wherein the implant comprises a monofilament fiber, the monofilament fiber having an elongation at break of 10% to 50%, and having one or more properties selected from the group consisting of a tensile strength of 400 MPa to 1200 MPa, and a Young's modulus of less than 3.0 GPa.
20. 20. The implant of claim 19, wherein the oriented form comprises a fiber, a mesh, a woven fabric, a nonwoven fabric, a film, a molding, a patch, a tube, a laminate, or a pultruded profile.
21. 21. The implant of claim 20, wherein the fiber is monofilament, braided, or barbed.
22. 21. The implant of claim 20, wherein the mesh, woven or nonwoven form is a knitted mesh, a woven mesh, or a monofilament mesh.
23. 20. The implant of claim 19, wherein the oriented configuration is uniaxially or biaxially oriented.
24. A medical implant comprising an oriented monofilament fiber derived from a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the monofilament fiber having an elongation at break of 10% to 50% and one or more properties selected from the group consisting of a tensile strength of 400 MPa to 1200 MPa, and a Young's modulus of less than 3.0 GPa, wherein when the implant is incubated in phosphate buffered saline at 37° C., (i) the weight average molecular weight of the polymer composition decreases by 3% to 13% over a 4 week period, (ii) the weight average molecular weight of the polymer composition decreases by 5% to 15% over a 8 week period, (iii) the weight average molecular weight of the polymer composition decreases by 10% to 30% over a 12 week period, (iv) the implant experiences a percentage mass loss of 0% to 5% over a 4 week period, or (v) the implant experiences a percentage mass loss of 0% to 5% over a 8 week period. Medical implants.
25. 25. The implant of claim 19 or 24, which is porous.
26. 25. The implant of claim 19 or 24, wherein the fibers have a tensile strength of 500 MPa to 1,200 MPa, 600 MPa to 1,200 MPa, or 700 MPa to 1,200 MPa.
27. 27. The implant of claim 24 or 26, wherein the fibers have a Young's Modulus of at least 600 MPa, 800 MPa, 1 GPa, or 2 GPa but less than 3 GPa.
28. 25. The implant of claim 24, wherein the fibers are knitted or woven into a mesh.
29. 29. The implant of claim 28, wherein (a) the mesh has a burst strength of from 1 kgf to 100 kgf, or from 10 kgf to 30 kgf, or (b) the Taber stiffness of the mesh is from 0.01 to 10 Taber stiffness units, or from 0.1 to 1 Taber stiffness units.
30. 25. The implant of claim 19 or 24, derived from a polymer composition further comprising: (a) one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) one or more of the following: a branching agent, a crosslinking agent, a chain extender, and a reactive blending agent; or (c) a hydroxycarboxylic acid unit having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups.
31. 31. The implant of claim 30, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid.
32. 25. The implant of claim 19 or 24 derived from a polymer composition comprising succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-citric acid copolyester, succinic acid-1,4-butanediol-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-citric acid copolyester, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyester, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof.
33. 25. The implant of claim 19 or 24, further comprising a plasticizer, a nucleating agent, a coating, a dye, a medical marker, a bioactive agent, a therapeutic agent, a diagnostic agent, a prophylactic agent, a contrast agent, a radiopaque marker, a radioactive material, an anti-adhesion agent, hyaluronic acid, an antibiotic, rifampin, minocycline, collagen, hydroxyapatite, or an absorbable polymer comprising one or more of the following monomers: glycolic acid, lactic acid, trimethylene carbonate, p-dioxanone, ε-caprolactone, 4-hydroxybutyric acid, and 3-hydroxybutyric acid.
34. 34. The implant of any one of claims 19 to 33, wherein the polymer composition does not contain urethane linkages and is not prepared with a diisocyanate.
35. 35. An implant according to any one of claims 19 to 34, wherein the polymer composition has a melting temperature of from 100°C to 150°C, or from 105°C to 120°C.
36. Sutures, barbed sutures, monofilament sutures, braided sutures, mesh sutures, wound closure devices, patches, wound healing devices, wound dressings, burn dressings, ulcer dressings, skin replacement materials, hemostatic materials, tracheal reconstruction devices, organ retrieval devices, dural patches or replacements, devices for nerve regeneration or repair, hernia repair devices, hernia repair meshes, hernia plugs, inguinal hernia plugs, devices for temporary wound or tissue support, scaffolds for tissue engineering, guided tissue repair / regeneration devices, anti-adhesion membranes or barriers, tissue isolation membranes, retention Sustainers, slings, pelvic floor reconstruction devices, devices for the treatment of pelvic organ prolapse, urethral suspension devices, devices for the treatment of urinary incontinence, devices for the treatment of stress urinary incontinence, bladder repair devices, expansion or filling devices, bone marrow scaffolds, bone plates, implant fixation devices, ligament repair or strengthening devices, anterior cruciate ligament repair devices, tendon repair or strengthening devices, rotator cuff repair devices, meniscus repair or regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, cardiovascular patches , catheter balloons, vascular closure devices, intracardiac septal defect repair devices including but not limited to atrial septal defect repair devices and PFO (patent foramen ovale) closure devices, left atrial appendage (LAA) closure devices, pericardial patches, venous valves, heart valves, vascular grafts, myocardial regeneration devices, periodontal meshes, guided tissue regeneration membranes for periodontal tissue, ophthalmic cell implants, imaging devices, cochlear implants, anastomosis devices, cell seeding devices, cell encapsulation devices, controlled release devices, drug delivery devices, plastic surgery devices, breast lift devices, mastopexy devices devices for breast reconstruction, devices for breast enlargement, devices for breast reduction, breast implants, devices for the removal, reshaping and reorientation of breast tissue, devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift, devices for eyelid lift, devices for face lift, devices for wrinkle removal, devices for thread lift, devices for lifting and supporting sagging areas of the face, eyebrows and neck, devices for rhinoplasty, devices for cheekbone enhancement, devices for earplasty, devices for neck lift,30. The implant of any one of claims 19, 24 and 29, selected from the group of genioplasty devices, buttocks lift devices, cosmetic repair devices and devices for facial scar correction.
37. 37. The implant of any one of claims 19 to 36, comprising less than 20 endotoxin units per implant as determined by a limulus amoebocyte lysate (LAL) assay.
38. 37. A method for making the implant of any one of claims 19, 24 and 36, wherein the polymer composition comprises 1,4-butanediol units and succinic acid units, the method comprising the steps of providing the polymer composition and performing any one of the following processes: casting, solvent casting, solution spinning, solution joining of fibers, melt processing, extrusion, melt extrusion, melt spinning, fiber spinning, orientation, relaxation, annealing, injection molding, compression molding, lamination, dry spinning, knitting, weaving, crocheting, melt blowing, film forming, film blowing, film casting, membrane forming, electrospinning, thermoforming, pultrusion, centrifugal spinning, molding, tube extrusion, spunbonding, nonwoven fabric making, stay forming, spunbonding ... forming or incorporating the polymer composition into an implant by one or more processes including: entangling of pulled fibers, knitting, weaving, and crocheting of fibers, mesh making, coating, dip coating, laser cutting, barb forming, punching, perforating, hole making, freeze drying, stitching, calendaring, lyophilization, phase separation, particle leaching, thermal phase separation, leaching, latex processing, gas plasma treatment, emulsion processing, 3D printing, fused filament manufacturing, fused pellet deposition, melt extrusion deposition, selective laser melting, printing of slurries and solutions using a coagulation bath, or printing using a binding solution and granules of powder.
39. 20. The implant of claim 19, adapted to promote healing of a wound, injury, or defect at a site on a patient, or to repair or regenerate tissue at a site on a patient, said implant being administered to said site.
40. 1. A surgical mesh implant comprising monofilament fibers derived from a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, the composition being optionally isotopically enriched, the monofilament fibers being oriented, having an elongation at break of 10% to 50%, and having one or more properties selected from the group consisting of a tensile strength of 400 MPa to 1200 MPa, and a Young's modulus of less than 3.0 GPa.
41. Below: (i) 5-800g / m 2 (ii) a suture pull-out strength of at least 10 N, or at least 20 N; (iii) pores having a diameter of at least 10 μm, at least 50 μm, or at least 100 μm; (iv) a burst strength of greater than 0.1 kPa; (v) a Taber stiffness of at least 0.01 Taber stiffness units; (vi) knitted, woven, crocheted, or braided fibers; and (vii) a degradation rate in phosphate buffered saline at 37° C. where the weight average molecular weight of the mesh decreases by 10% to 30% over a 12 week period.
42. 42. The implant of claim 41, comprising fibers having one or more of the following properties: (iii) a tensile strength of from 4 g / denier to 12 g / denier, (iv) a Young's modulus of from 600 MPa to 3.0 GPa, (v) a diameter of from 10 μm to 1 mm, (vi) a melting temperature of from 100 to 150°C or from 105°C to 120°C, and (vii) a degradation rate in phosphate buffered saline at 37°C such that the weight average molecular weight of the fibers decreases by from 10% to 25% over a period of 12 weeks.
43. 41. The surgical mesh implant of claim 40, wherein the implant has a burst strength of greater than 0.1 kPa, the implant comprising fibers having a Young's Modulus of at least 600 MPa, at least 1 GPa, or at least 2 GPa.
44. 44. The implant of claim 43, comprising fibers having one or more of the following properties: tensile strength of 400 MPa to 1,200 MPa, tensile strength of 4 g / denier to 12 g / denier, Young's modulus less than 3.0 GPa, elongation at break of 10% to 50%, diameter of 10 μm to 1 mm, melt temperature of 100-150° C. or 105° C. to 120° C., or said fibers are prepared by melt extrusion from a polymer composition comprising 1,4-butanediol units and succinic acid units, said polymer composition having a weight average molecular weight of 75,000 to 300,000.
45. The mesh has the following characteristics: 5 to 800 g / m 2 44. The implant of claim 43, having one or more of: an areal density of at least 10 N, or at least 20 N; a suture pull-out strength of at least 10 N, or at least 20 N; and pores having a diameter of at least 10 μm, at least 50 μm, or at least 100 μm.
46. 44. The implant of claim 43, comprising monofilament fibres, said monofilament fibres being stretched to orient said fibres, said fibres having a Young's Modulus of at least 600 MPa, at least 800 MPa, or at least 1 GPa, and optionally said fibres having a diameter of from 10 μm to 1 mm.
47. 47. The implant of claim 46, wherein the fibers have a Young's Modulus of less than 3 GPa, or the fibers have a Young's Modulus of greater than 1.5 GPa or 2.0 GPa but less than 3 GPa.
48. 47. The implant of claim 43 or 46, wherein the fibers are oriented with an orientation ratio of at least 6.0, at least 6.5, or at least 7.
0.
49. 47. The implant of any one of claims 40, 43 and 46, wherein the polymer composition used to prepare the implant further comprises: (a) one or more of the following: a second diacid unit, a second diol unit, 1,3-propanediol, ethylene glycol, 1,5-pentanediol, glutaric acid, adipic acid, terephthalic acid, malonic acid, and oxalic acid; (b) one or more of the following, excluding diisocyanate agents and agents that incorporate urethane linkages in the polymer composition: branching agents, crosslinking agents, chain extenders, and reactive blending agents; (c) a hydroxycarboxylic acid unit having two carboxyl groups and one hydroxyl group, two hydroxyl groups and one carboxyl group, three carboxyl groups and one hydroxyl group, or two hydroxyl groups and two carboxyl groups.
50. 50. The implant of claim 49, wherein the branching, crosslinking, or chain extender units are selected from one or more of the following: malic acid, maleic acid, fumaric acid, trimethylolpropane, trimesic acid, citric acid, glycerol propoxylate, and tartaric acid.
51. 47. The implant of any one of claims 40, 43 and 46, wherein the polymer composition used to prepare the implant comprises succinic acid-1,4-butanediol-malic acid copolyester, succinic acid-1,4-butanediol-citric acid copolyester, succinic acid-1,4-butanediol-tartaric acid copolyester, succinic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof, succinic acid-adipic acid-1,4-butanediol-malic acid copolyester, succinic acid-adipic acid-1,4-butanediol-citric acid copolyester, succinic acid-adipic acid-1,4-butanediol-tartaric acid copolyester, or succinic acid-adipic acid-1,4-butanediol-malic acid copolyester further comprising citric acid, tartaric acid, or a combination thereof.
52. 52. The implant of any one of claims 49 to 51, which does not contain urethane linkages and is not prepared with a diisocyanate.
53. 53. An implant according to any one of claims 40 to 52, having a melting temperature of from 100°C to 150°C, or from 105°C to 120°C.
54. (a) the surgical mesh is a knitted mesh, woven mesh, crocheted mesh, monofilament mesh, weft knit mesh, warp knit mesh, plug, hernia plug, void filler, inguinal hernia plug, and has a three-dimensional shape that can be temporarily deformed as needed or has an outwardly curving exterior and an inwardly curving interior; (b) the surgical mesh further comprises an anti-adhesion layer, barbs, hooks, self-anchoring tips, microgrips, fleece, reinforcing materials, and reinforced outer edges or borders; or (c) the surgical mesh is 47. The implant of any one of claims 40, 43 and 46, further comprising a plasticizer, a nucleating agent, a coating, a dye, a medical marker, a bioactive agent, a therapeutic agent, a diagnostic agent, a prophylactic agent, a contrast agent, a radiopaque marker, a radioactive material, an anti-adhesion agent, hyaluronic acid, an antibiotic, rifampin, minocycline, collagen, hydroxyapatite, or an absorbable polymer comprising one or more of the following monomers: glycolic acid, lactic acid, trimethylene carbonate, p-dioxanone, ε-caprolactone, 4-hydroxybutyric acid, and 3-hydroxybutyric acid.
55. The implant is a wound closure device, a patch, a wound healing device, a device for tissue or suture reinforcement, a tracheal reconstruction device, an organ retrieval device, a dural patch or replacement, a device for nerve regeneration or repair, a hernia repair device, a hernia mesh, a hernia plug, an inguinal hernia plug, a device for temporary wound or tissue support, a tissue engineering scaffold, a guided tissue repair / regeneration device, an anti-adhesion membrane or barrier, a tissue separation membrane, a retention membrane, a sling, a device for pelvic floor reconstruction, a device for the treatment of pelvic organ prolapse. , urethral suspension devices, devices for the treatment of urinary incontinence, bladder repair devices, void filling devices, bone marrow scaffolds, ligament repair or strengthening devices, anterior cruciate ligament repair devices, tendon repair or strengthening devices, rotator cuff repair devices, meniscus repair or regeneration devices, articular cartilage repair devices, osteochondral repair devices, spinal fixation devices, cardiovascular patches, vascular closure devices, intracardiac septal defect repair devices, atrial septal defect repair devices, patent foramen ovale closure devices, left atrial appendage closure devices, pericardial patches, vascular grafts, cardiac Muscle regeneration devices, periodontal meshes, guided tissue regeneration membranes for periodontal tissue, imaging devices, anastomosis devices, devices for cell seeding, devices for controlled release, devices for drug delivery, plastic surgery devices, devices for breast lift, devices for mastopexy, devices for breast reconstruction, devices for breast enlargement, breast implants, devices for breast reduction, devices for breast reconstruction after mastopexy with or without breast implants, devices for facial reconstruction, devices for forehead lift, devices for eyebrow lift, devices for eyelid lift, devices for face lift, devices for rhytidectomy, devices for rhinoplasty devices, devices for cheekbone augmentation, devices for otoplasty, devices for neck lift, devices for chinplasty, devices for buttock lift, devices for cosmetic repair, devices for facial scar correction, pouches, holders, covers, housings or casings which partially or completely encase, surround or hold implantable medical devices, cardiac rhythm management devices, pacemakers, defibrillators, generators, implantable access systems, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medicines and fluids, intrathecal delivery systems, pain pumps,or a device that provides a drug or electrical stimulation to the body.
56. 56. A method of making the surgical mesh implant of any one of claims 40-55, wherein the mesh comprises fibers, the method comprising melt spinning a polymer composition comprising 1,4-butanediol units and succinic acid units to obtain extruded fibers, quenching the extruded fibers, heating the fibers, and drawing the fibers in multiple stages.
57. The method comprises the steps of: (i) quenching the extruded fiber in a water bath at a temperature between 40° C. and 70° C.; (ii) cooling the extruded fiber after quenching without stretching; (iii) drawing the cooled extruded fiber in a chamber containing a thermally conductive liquid to an orientation ratio of at least 3.0 at a temperature between 50° C. and 70° C.; (iv) drawing the fiber after the initial drawing in one or more further drawing steps to an orientation ratio of at least 2.0 in a chamber containing a thermally conductive liquid at a temperature between 60° C. and 80° C.; (v) drawing the extruded fiber in multiple stages at gradually increasing temperatures.
57. The method of claim 56, comprising one or more of the steps of: (vi) drawing the extruded fiber in a chamber containing a thermally conductive liquid at multiple stages of gradually increasing temperature; (vii) drawing the fiber without the use of a heated oven; (viii) extruding the fiber at a temperature between 80°C and 180°C; (ix) extruding the fiber at a temperature below 230°C or below 200°C; (x) drying the polymer composition prior to melt spinning to provide a moisture content of the polymer composition of less than 0.1 wt%, less than 0.05 wt%, or less than 0.005 wt%.
58. 57. The method of claim 56, further comprising: (a) the polymer composition has a melting temperature of 100°C to 150°C, or 105°C to 120°C; (b) the fibers are prepared by solvent spinning or 3D printing; or (c) drying the polymer composition to a water content of less than 0.1 wt%, less than 0.05 wt%, or less than 0.005 wt%.
59. 56. An implant as described in any one of claims 49 to 55 for promoting healing of a wound, injury or defect at a patient site or for repairing, lifting or reconstructing tissue at a patient site, wherein the implant is administered to the site.
60. 60. The implant of claim 59, wherein the implant is delivered by one or more of the following methods: a minimally invasive approach, a laparoscopic approach, temporary deformation of the implant, and insertion of the implant through an insertion tool.
61. 60. The implant of claim 59, wherein (a) the implant conforms to the patient's anatomical shape, (b) the implant does not curl at the edges after implantation, (c) there are no indentations on the surface of the implant for a period of four weeks after administration of the implant to the site, and (d) the dimensions of the implant do not shrink by more than 5% from their initial values in any direction.
62. The implant is used in hernia repair, inguinal hernia repair, femoral hernia repair, incisional hernia repair, ventral hernia repair, umbilical hernia repair, wound management, reinforcement, tracheal reconstruction, organ retrieval, dura repair, nerve regeneration or repair, tissue engineering, guided tissue repair or regeneration, anti-adhesion or tissue separation applications, sling surgery, pelvic floor reconstruction, urethral suspension, treatment of urinary incontinence, bladder repair, void filling, bone marrow replacement, ligament repair device or reinforcement, anterior cruciate ligament repair, tendon repair or reinforcement, rotator cuff repair, meniscus repair or regeneration, articular cartilage repair, osteochondral repair, spinal fixation, cardiovascular patching, blood vessel closure, intracardiac septal defect repair, atrial septal defect repair, patent foramen ovale closure, left atrial appendage closure, pericardial patching, vascular grafts, myocardial regeneration, guided tissue regeneration of periodontal tissue, 61. The implant of claim 59 or 60 for use in imaging, anastomosis, cell seeding, controlled release, drug delivery, plastic surgery, breast lift, mastopexy, breast reconstruction, breast augmentation, breast reduction, breast reconstruction after mastopexy with or without breast implants, facial reconstruction, forehead lift, brow lift, eyelid lift, face lift, rhytidectomy, rhinoplasty, cheekbone augmentation, otoplasty, neck lift, chinplasty, buttock lift, cosmetic repair, facial scar correction, and complete or partial encapsulation of implantable medical devices, cardiac rhythm management devices, pacemakers, defibrillators, generators, implantable access systems, neurostimulators, ventricular access devices, infusion pumps, devices for the delivery of medicines and fluids, intrathecal delivery systems, pain pumps, or devices that provide drugs or electrical stimulation to the body.
63. 1. A monofilament fiber derived from a polymer composition, the polymer composition comprising 1,4-butanediol units and succinic acid units, having an endotoxin content of less than 2.5 EU / g, and optionally being isotopically enriched, the monofilament fiber being oriented, having an elongation at break of 10% to 50%, and having one or more properties selected from the group consisting of a tensile strength of 400 MPa to 1200 MPa, and a Young's modulus of less than 3.0 GPa, and the polymer composition does not comprise urethane linkages and is not prepared with a diisocyanate.
Citation Information
Patent Citations
Suture for operation and its manufacture
JP1996317968A
Suture thread
JP1998099424A
Coating agent for improving nodus strength of absorptive monofilament suture
JP2000102599A
Biodegradable polyester copolymers
US20100249332A1
Polyester fibers
US5349028A